Lithium-ion secondary battery
By introducing the grain boundaries of magnesium and oxygen into the positive electrode active material particles of lithium-ion secondary batteries and controlling the content of fluorine, the shortcomings in existing batteries in terms of capacity, circulation characteristics and safety are solved, and the low degradation of materials and high safety and reliability of batteries are achieved.
Patent Information
- Application Number
- JP2024044308
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-05-12
- Filing Date
- 2024-03-20
- Publication Date
- 2025-04-14
- Estimated Expiration
- 2038-05-01
AI Technical Summary
There is room for improvement in existing lithium-ion secondary batteries and positive electrode active materials in terms of capacity, circulation characteristics, reliability, safety and cost.
A positive electrode active material particle consisting of the first and second grains is used, wherein the grain boundaries contain magnesium and oxygen, and may further contain fluorine, and the atomic concentration ratio of magnesium and fluorine is controlled within a specific range to improve the stability and performance of the material.
Low degradation of positive electrode active material particles is achieved, and new positive electrode active material is provided, which improves the safety and long-term reliability of the battery, and reduces the degradation speed of the battery.
Smart Images

Figure 0007661565000003 
Figure 0007661565000004 
Figure 0007661565000005
Abstract
Description
[Technical field]
[0001] One aspect of the present invention relates to an object, a method, or a manufacturing method. Process, machine, manufacture, or composition of matter One embodiment of the present invention relates to a semiconductor device, a display device, a light-emitting device, a power storage device, a lighting device, or a The present invention relates to a method for manufacturing an electronic device. In particular, the present invention relates to a positive electrode active material that can be used in a secondary battery, a secondary The present invention relates to a battery and an electronic device having a secondary battery.
[0002] In this specification, the term "electricity storage device" refers to elements and devices having an electricity storage function in general. For example, lithium ion secondary batteries and other storage batteries (also called secondary batteries) These include lithium ion capacitors and electric double layer capacitors.
[0003] In addition, in this specification, the term "electronic device" refers to any device having a power storage device. Electro-optical devices having a power storage device, and information terminal devices having a power storage device are all electronic devices. [Background technology]
[0004] In recent years, various types of storage devices such as lithium-ion secondary batteries, lithium-ion capacitors, and air batteries have become available. The development of lithium-ion secondary batteries, which have high output and capacity, is particularly popular. Mobile phones, smartphones, notebook computers and other portable information terminals, portable music devices Players, digital cameras, medical equipment, or hybrid vehicles (HEVs), electric vehicles ( Next-generation clean energy such as electric vehicles (EV) or plug-in hybrid vehicles (PHEV) Demand for rechargeable energy has expanded rapidly along with the development of the semiconductor industry, including automobiles. It has become an indispensable source of information in today's information society.
[0005] Therefore, in order to improve the cycle characteristics and increase the capacity of lithium-ion secondary batteries, Improvements to active materials have been investigated (Patent Documents 1 and 2).
[0006] In addition, the characteristics required for an energy storage device are safety in various operating environments and long-term reliability. Improvements include: [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2012-018914 A [Patent Document 2] JP 2016-076454 A Summary of the Invention [Problem to be solved by the invention]
[0008] Lithium ion secondary batteries and the positive electrode active materials used therein have the following characteristics: capacity, cycle characteristics, Improvements are desired in various aspects, such as charge / discharge characteristics, reliability, safety, and cost.
[0009] In view of the above, an object of one embodiment of the present invention is to provide positive electrode active material particles that are less deteriorated. Another object of one embodiment of the present invention is to provide a novel positive electrode active material particle. Another object of one embodiment of the present invention is to provide a power storage device that is less susceptible to deterioration. Another object of one embodiment of the present invention is to provide a highly safe power storage device. Another object of one embodiment of the present invention is to provide a novel power storage device.
[0010] The description of these problems does not preclude the existence of other problems. It is not necessary for the embodiment to solve all of these problems. It is possible to extract problems other than those mentioned above from the description of the claim. [Means for solving the problem]
[0011] One aspect of the present invention is a method for manufacturing a crystal grain having a first crystal grain, a second crystal grain, and a crystal grain having a first crystal grain and a second crystal grain. and a grain boundary located therebetween, the first grain and the second grain being in contact with lithium and a transition metal. A positive electrode active material having a metal and oxygen, and a crystal grain boundary having magnesium and oxygen. It is a particle.
[0012] In the above-mentioned positive electrode active material particles, the atomic concentration of magnesium relative to the atomic concentration of the transition metal It is preferable that the ratio is in the range of 0.010 or more and 0.50 or less.
[0013] In the above-mentioned positive electrode active material particles, the crystal grain boundaries preferably further contain fluorine.
[0014] In the above-mentioned positive electrode active material particles, the ratio of the atomic concentration of fluorine to the atomic concentration of the transition metal is , preferably in the range of 0.020 or more and 1.00 or less.
[0015] The positive electrode active material particles contain transition metals such as iron, cobalt, nickel, manganese, and chromium. It is preferable that the alloy contains at least one of titanium, vanadium and niobium. Effect of the Invention
[0016] According to one embodiment of the present invention, a positive electrode active material particle that is less likely to deteriorate can be provided. It is possible to provide a substance particle. It is also possible to provide a power storage device with little deterioration. It is also possible to provide a highly safe It is possible to provide a power storage device. It is also possible to provide a novel power storage device. [Brief description of the drawings]
[0017] [Figure 1] 4A to 4C are diagrams illustrating an example of a positive electrode active material particle. [Diagram 2] FIG. 4 is a diagram illustrating a concentration distribution in a positive electrode active material particle. [Diagram 3] 4A to 4C are diagrams illustrating an example of a method for manufacturing positive electrode active material particles. [Figure 4] FIG. 13 is a cross-sectional view of an active material layer in the case where a graphene compound is used as a conductive assistant. [Diagram 5] FIG. 2 is a diagram illustrating a coin-type secondary battery. [Figure 6] FIG. 2 is a diagram illustrating a cylindrical secondary battery. [Figure 7] 1A and 1B are diagrams illustrating examples of secondary batteries. [Figure 8] 1A and 1B are diagrams illustrating examples of secondary batteries. [Figure 9] 1A and 1B are diagrams illustrating examples of secondary batteries. [Figure 10] 1A and 1B are diagrams illustrating examples of secondary batteries. [Figure 11] 1A and 1B are diagrams illustrating examples of secondary batteries. [Figure 12] FIG. 1 is a diagram illustrating a laminated secondary battery. [Figure 13] FIG. 1 is a diagram illustrating a laminated secondary battery. [Figure 14] FIG. 2 is a diagram showing the appearance of a secondary battery. [Figure 15] FIG. 2 is a diagram showing the appearance of a secondary battery. [Figure 16] 1A to 1C are diagrams illustrating a method for manufacturing a secondary battery. [Figure 17] 1A and 1B are diagrams illustrating a bendable secondary battery. [Figure 18] 1A and 1B are diagrams illustrating a bendable secondary battery. [Figure 19] 1A to 1C are diagrams illustrating examples of electronic devices. [Figure 20] 1A to 1C are diagrams illustrating examples of electronic devices. [Figure 21] 1A to 1C are diagrams illustrating examples of electronic devices. [Figure 22] 1A to 1C are diagrams illustrating examples of electronic devices. [Diagram 23] 1A and 1B are TEM images and schematic diagrams of cross sections of positive electrode active material particles according to an example. [Figure 24] 4 is a STEM image of a cross section of a positive electrode active material particle according to an example. [Diagram 25] 4A to 4C are diagrams illustrating an HAADF-STEM image and an EDX point analysis of a positive electrode active material particle according to an example. [Figure 26] FIG. 4 shows EDX spectra and quantitative results of positive electrode active material particles according to an example. [Figure 27] FIG. 4 shows EDX spectra and quantitative results of positive electrode active material particles according to an example. [Figure 28] FIG. 4 shows EDX spectra and quantitative results of positive electrode active material particles according to an example. [Figure 29] FIG. 4 shows EDX spectra and quantitative results of positive electrode active material particles according to an example. [Diagram 30] FIG. 4 shows EDX spectra and quantitative results of positive electrode active material particles according to an example. [Diagram 31] 1 is a mapping image in EDX area analysis of positive electrode active material particles according to an example. [Diagram 32] 1 is a mapping image in EDX area analysis of positive electrode active material particles according to an example. [Diagram 33] FIG. 4 is a diagram illustrating an EDX line analysis of the positive electrode active material particles according to the example. [Diagram 34] FIG. 4 is a graph showing atomic concentrations in EDX line analysis of the positive electrode active material particles according to the example. [Diagram 35] FIG. 4 is a graph showing atomic concentrations in EDX line analysis of the positive electrode active material particles according to the example. [Diagram 36] FIG. 4 is a graph showing the ratio of the number of atoms in EDX line analysis of the positive electrode active material particles according to the example. [Figure 37] 1 is a mapping image in EDX area analysis of positive electrode active material particles according to an example. [Figure 38] 1 is a mapping image in EDX area analysis of positive electrode active material particles according to an example. [Figure 39]FIG. 4 is a graph showing atomic concentrations in EDX line analysis of the positive electrode active material particles according to the example. [Diagram 40] FIG. 4 is a graph showing atomic concentrations in EDX line analysis of the positive electrode active material particles according to the example. [Diagram 41] FIG. 4 is a graph showing the ratio of the number of atoms in EDX line analysis of the positive electrode active material particles according to the example. [Diagram 42] 1A and 1B are TEM images and schematic diagrams of cross sections of positive electrode active material particles according to an example. [Diagram 43] 4 is a STEM image of a cross section of a positive electrode active material particle according to an example. [Diagram 44] 1 is a mapping image in EDX area analysis of positive electrode active material particles according to an example. [Diagram 45] 1 is a mapping image in EDX area analysis of positive electrode active material particles according to an example. [Diagram 46] FIG. 4 is a diagram illustrating an EDX line analysis of the positive electrode active material particles according to the example. [Figure 47] FIG. 4 is a graph showing atomic concentrations in EDX line analysis of the positive electrode active material particles according to the example. [Figure 48] FIG. 4 is a graph showing atomic concentrations in EDX line analysis of the positive electrode active material particles according to the example. [Figure 49] FIG. 4 is a graph showing the ratio of the number of atoms in EDX line analysis of the positive electrode active material particles according to the example. [Figure 50] 1 is a mapping image in EDX area analysis of positive electrode active material particles according to an example. [Figure 51] 1 is a mapping image in EDX area analysis of positive electrode active material particles according to an example. [Figure 52] FIG. 4 is a graph showing atomic concentrations in EDX line analysis of the positive electrode active material particles according to the example. [Diagram 53] FIG. 4 is a graph showing atomic concentrations in EDX line analysis of the positive electrode active material particles according to the example. [Figure 54] FIG. 4 is a graph showing the ratio of the number of atoms in EDX line analysis of the positive electrode active material particles according to the example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. The present invention is not limited to the following description, and various modifications in form and details are possible by those skilled in the art. The present invention is not limited to the description of the following embodiments. It is not something that can be done.
[0019] In each of the drawings described in this specification, the positive electrode, the negative electrode, the active material layer, the separator, the exterior body, etc. The size and thickness of each component may be exaggerated for clarity of description. Therefore, each component is not necessarily limited by its size, and the correlation between each component is not necessarily limited by its size. It is not limited to the relative size.
[0020] In addition, in the configuration of the present invention described in this specification, etc., the same parts or parts having similar functions The same reference numerals are used in common between different drawings, and the repeated explanations are omitted. When referring to parts having similar functions, the same hatch pattern is used and no special reference numerals are attached. There may not be.
[0021] In addition, crystal planes and directions are indicated by superscript bars in crystallography. The crystal planes and directions in are indicated by a bar above the numbers instead of the numbers due to the limitations of the application. The numbers are expressed by adding a minus sign (-) before them. Also, individual orientations that indicate directions within a crystal is [ ], a collective orientation showing all equivalent directions is < >, and an individual face showing a crystal face is ( ) and set faces with equivalent symmetry are represented by {}.
[0022] In this specification, segregation refers to a solid that contains multiple elements (e.g., A, B, C). This refers to the phenomenon in which the concentration of a certain element (e.g. B) is distributed unevenly.
[0023] (Embodiment 1) [Positive electrode active material structure] A positive electrode active material particle 100 according to one embodiment of the present invention is shown in FIG. The following will be explained with reference to Figures 2(A) to 2(C).
[0024] FIG. 1(A) shows the appearance of a positive electrode active material particle 100. The positive electrode active material particle 100 is an amorphous The shape of the positive electrode active material particle 100 shown in FIG. 1(A) is just one example. Not limited to.
[0025] The positive electrode active material particle 100 has a plurality of crystal grains 101 and a plurality of crystal grain boundaries 103. FIG. 1B shows crystal grains 101 and crystal grain boundaries 103 of the positive electrode active material particle 100. In (B), the grain boundary 103 is shown by a dashed line. In addition, the boundaries of the crystal grains 101 and the crystal grain boundaries 102 shown in FIG. The shape and number of 03 are merely examples and are not limited to these.
[0026] The crystal grains 101 are particles in which the crystal orientation within the crystal grain is approximately uniform. Each of the crystal grains has a different crystal orientation, and there is a crystal grain boundary 103 between adjacent crystal grains. That is, the positive electrode active material particle 100 has a plurality of crystal grains 101 with a crystal grain boundary 103 therebetween. The positive electrode active material particles 100 can also be said to be polycrystalline. It may have a recess 105 or an amorphous region. Crystal defects are bulk defects, plane defects, point defects, or defects caused by other elements in the crystal that can be observed in a TEM image. It refers to a structure in which crystal grains are embedded. Note that crystal grains are sometimes called crystallites.
[0027] The crystal grains 101 and the crystal grain boundaries 103 in the positive electrode active material particles 100 were confirmed by X-ray diffraction (XR D: X-ray Diffraction, Neutron Diffraction, Electron Diffraction (ED: Electron ctron diffraction), transmission electron microscope (TEM) sion Electron Microscope image, Scanning Transmission Electron Microscope (STE M:Scanning Transmission Electron Microsc Fast Fourier transform (FFT) of lattice images obtained from opy images, TEM images, or STEM images FT: Fast Fourier Transformation) analysis, high angle scattering High-Angle Annul Scanning Transmission Electron Microscope (HAADF-STEM) ar Dark Field Scanning TEM) image, Annular bright field scanning transmission electron Microscope (ABF-STEM: Annular Bright-Field Scanning) ng TEM image, Raman spectroscopy, electron backscattering Electron Backscatter Diffraction (EBSD) Electron backscatter diffraction (EBSP) and other methods can be used. on Backscatter Diffraction Pattern) For example, if the density (brightness) of a TEM image is approximately uniform, it is considered to be a crystalline substance. In some cases, the crystal orientation is almost uniform, meaning that it can be determined to be a single crystal. Since the density (brightness) of the TEM image differs depending on the material, the area where the density (brightness) changes is determined to be the grain boundary. However, it is not always possible to distinguish between the grains 101 and the grain boundaries 102 by various analyses. It is not necessary to observe a clear boundary of 03.
[0028] The grains 101 and the grain boundaries 103 have different compositions. The grain boundaries 103 contain magnesium and oxygen. The grain boundary 103 preferably further contains fluorine.
[0029] The crystal grains 101 and the crystal grain boundaries 103 were analyzed by energy dispersive X-ray analysis (EDX). Dispersive X-ray Spectroscopy (DXS), Time-of-Flight Secondary Imaging Time-of-Flight Secondary Integral Mass Spectroscopy (ToF-SIMS) ion mass spectrometry), X-ray photoelectron spectroscopy (XPS:X-ra y Photoelectron Spectroscopy), Auger Electron Spectroscopy (A ES: Auger Electron Spectroscopy, electron energy loss Electron Energy-Loss Spectrosc (EELS) However, it is possible to confirm that the composition of the material differs depending on the analysis method. Therefore, it is not necessary to clearly observe the boundaries between the crystal grains 101 and the crystal grain boundaries 103. However, depending on the analytical method, the desired target element may not be detected. Even when the concentration of the target element is extremely low, the target element may not be detected. be.
[0030] <Grain boundary> The grain boundaries 103 of the positive electrode active material particles 100 according to one embodiment of the present invention are formed of magnesium and The grain boundaries 103 contain magnesium oxide and oxygen. It is preferable that magnesium oxide further contains fluorine. A part of oxygen in magnesium oxide is replaced with fluorine. By partially substituting magnesium oxide with fluorine, for example, The diffusibility of lithium can be increased, and charging and discharging are not hindered. The grain boundary 103 contains fluorine. This may make it less soluble in hydrofluoric acid.
[0031] Compared to the grains 101, the grain boundaries 103 have regions with a higher magnesium concentration. It can also be said that the grain boundary 103 has a region where magnesium is segregated.
[0032] Compared to the grains 101, the grain boundaries 103 have regions with a higher fluorine concentration. It can also be said that 03 has a region where fluorine is segregated.
[0033] The magnesium concentration distribution between the dashed dotted lines A1-A2 of the positive electrode active material particle 100 shown in FIG. An example of the fabric is shown in FIG. 2(B), and an example of the fluorine concentration distribution is shown in FIG. 2(C). In (C), the horizontal axis indicates the distance between the dashed lines A1 and A2 in FIG. 2(A), and the vertical axis indicates Magnesium concentration (Mg Concentration) and fluorine concentration (F Concentration).
[0034] Compared to the grains 101, the grain boundaries 103 and the vicinity of the grain boundaries 103 are rich in magnesium and The crystal defect 105 also has a region where the concentration of fluorine is high. In some cases, there may be a region where the concentration of fluorine is high. Note that in FIG. 2(B) and FIG. 2(C), 1, the grain boundaries 103 and the crystal defects 105 have the same concentration. In addition, the shape of the magnesium and fluorine concentration distribution is similar to that shown in Figure 2(B) and Figure 2(C). It is not limited to the shape shown.
[0035] Here, the number of transition metal atoms in the crystal grain 101 is represented as Tr-Metal. The number of transition metal atoms (Tr-Metal) in 1 is the number of atoms of each transition metal in the crystal grain 101. Refers to the total number of children.
[0036] The positive electrode active material particle 100 has a grain boundary 101 with respect to the number of transition metal atoms in the grain 101. The ratio of the number of magnesium atoms in 03 (Mg / Tr-Metal) is 0.010 or more It is preferable that the positive electrode active material particles 100 have a region of Mg 0.50 or less. It is preferable that / Tr-Metal is in the range of 0.020 or more and 0.30 or less. In the positive electrode active material particles 100, Mg / Tr-Metal is 0.030 or more and 0.20 or less. By using the above-mentioned Mg / Tr-Metal, the positive electrode active material In other words, deterioration of the power storage device can be suppressed. The present invention can be an apparatus.
[0037] In this specification, the term "transition metal" refers to elements belonging to Groups 3 to 12 of the periodic table. The above group numbers are based on the International Union of Pure and Applied Chemistry (IUPAC). Union of Pure and Applied Chemistry Based on the periodic table classified into groups 1 to 18 in the revised mechanical chemical nomenclature (1989) Made.
[0038] Generally, as the power storage device is repeatedly charged and discharged, the positive electrode active material particles in the power storage device lose carbon. Transition metals such as barium and manganese dissolve into the electrolyte, oxygen is released, and the crystal structure becomes unstable. This can cause side reactions such as the above, which can accelerate the deterioration of the positive electrode active material particles. As a result of the deterioration of the capacitor, the capacity of the power storage device may decrease. In the fine print, the transition metal of the positive electrode active material particles dissolves into the electrolyte, oxygen is released, and crystallization occurs. Positive electrode active material particles undergo chemical and structural changes, such as their structure becoming unstable. In this specification and the like, a decrease in the capacity of the power storage device is sometimes referred to as deterioration of the power storage device. This is sometimes called equipment deterioration.
[0039] Metals eluted from the positive electrode active material particles are reduced and precipitated at the negative electrode, interfering with the electrode reaction at the negative electrode. Metal deposition on the negative electrode can lead to deterioration such as a decrease in capacity.
[0040] The insertion and removal of lithium during charging and discharging causes the crystal lattice of the positive electrode active material particles to expand and contract. The volume change and distortion of the crystal lattice may occur. This can cause the positive electrode active material particles to crack, which can lead to deterioration such as a decrease in capacity. Cracks in active material particles may start from grain boundaries.
[0041] If the temperature inside the energy storage device becomes too high and oxygen is released from the positive electrode active material particles, the safety of the energy storage device will be compromised. In addition, the crystal structure of the positive electrode active material particles may be damaged by the release of oxygen. The charge and discharge process may cause deterioration such as a decrease in capacity. Oxygen may also be released from the positive electrode active material particles due to the release of oxygen.
[0042] On the other hand, magnesium oxide is a chemically and structurally stable material. In the case of the above-mentioned electric storage device, the magnesium oxide contained in the positive electrode active material particles does not itself have a battery capacity. It is not involved in the reaction. In other words, magnesium oxide makes it difficult for lithium to be inserted or removed. Therefore, magnesium oxide itself is chemically and structurally stable even after being charged and discharged.
[0043] The positive electrode active material particle 100 according to one embodiment of the present invention has magnesium oxide at the crystal grain boundary 103. As a result, the positive electrode active material particles 100 are chemically and structurally stable, and structural changes caused by charging and discharging are prevented. In other words, the crystal structure of the positive electrode active material particles 100 is stable. This makes it possible to suppress the transformation of the crystal structure even when the charge and discharge are repeated. This can suppress cracking of the particles 100. In other words, this is preferable because it can suppress deterioration such as a decrease in capacity. When the charge voltage is high and the amount of lithium present in the positive electrode becomes smaller during charging, the crystal structure The crystal structure of the positive electrode active material particle 100 according to one embodiment of the present invention becomes unstable and easily deteriorates. This is particularly preferable because the structure is more stable and deterioration such as a decrease in capacity can be suppressed.
[0044] The positive electrode active material particle 100 according to one embodiment of the present invention has a stable crystal structure, and therefore is It is possible to prevent transition metals from eluting from the material particles, which means that deterioration such as capacity loss can be suppressed. Yes, it is preferable.
[0045] In addition, when the positive electrode active material particle 100 according to one embodiment of the present invention is cracked along the grain boundary, the crack The surface of the positive electrode active material particles after cracking has magnesium oxide. In terms of the quality, side reactions can be suppressed, and deterioration of the positive electrode active material can be reduced. This can suppress the degradation.
[0046] The positive electrode active material particle 100 according to one embodiment of the present invention has magnesium oxide at the crystal grain boundary 103. This suppresses the oxygen contained in the positive electrode active material particles 100 from diffusing through the grain boundaries. It is possible to suppress the release of oxygen from the positive electrode active material particles 100. In this way, a highly safe power storage device can be provided.
[0047] In addition, when the crystal defect 105 contains magnesium oxide, the crystal structure of the positive electrode active material particle 100 is stabilized and is preferred.
[0048] The positive electrode active material particle 100 has a grain boundary 101 with respect to the number of transition metal atoms in the grain 101. The ratio of the number of fluorine atoms in 03 (F / Tr-Metal) is 0.020 or more and 1.00 or less. It is preferable that the positive electrode active material particles 100 have the following region. It is preferable that the etal is in the range of 0.040 or more and 0.60 or less. The active material particles 100 have an F / Tr-Metal range of 0.060 or more and 0.40 or less. By using the above-mentioned F / Tr-Metal, the grain boundaries and their vicinity are Magnesium can be efficiently segregated. In other words, deterioration of the positive electrode active material can be reduced. Deterioration of the device can be suppressed. In addition, a highly safe power storage device can be provided.
[0049] <Crystal grain> The crystal grains 101 of the positive electrode active material particles 100 according to one embodiment of the present invention are made of lithium, transition metals, and the like. For example, the crystal grain 101 is a complex acid containing lithium, a transition metal, and oxygen. The transition metals include iron, cobalt, nickel, manganese, chromium, and titanium. One or more of tungsten, vanadium, niobium, and the like can be used.
[0050] The crystal grains 101 have, for example, a layered rock salt type crystal structure or a spinel type crystal structure. The crystal grains 101 may be made of, for example, a polyanion. A polyanion-based positive electrode material can be used. For example, olivine can be used as a polyanion-based positive electrode material. The crystal structure of the material may be a crystalline structure of the Nasicon type, a crystalline structure of the material may be a crystalline structure of the Nasicon type, or a crystalline structure of the material may be a crystalline structure of the material. For example, a cathode material containing sulfur can be used.
[0051] Various composite oxides can be used as the crystal grains 101. For example, LiFeO2, LiCoO2, LiNiO2, LiMn2O4, Li2MnO3, V2O5, Cr2O5 Compounds such as MnO2 can be used.
[0052] As an example of a material with a layered rock salt type crystal structure, a composite oxide represented by LiMO2 is used. The element M is preferably at least one selected from Co and Ni. LiCoO2 has a large capacity, is stable in air, and is relatively thermally stable. In addition, the element M is preferably selected from Co and Ni. In addition to one or more of these, it may also contain one or more selected from Al and Mn.
[0053] For example, LiNi x Mn y Co z O w (x, y, z and w are, for example, x=y=z = 1 / 3 or nearby, w = 2 or nearby) can be used. , LiNi x Mn y Co z O w (x, y, z and w are, for example, x=0.8 or its vicinity, y=0.1 or its vicinity, z=0.1 or its vicinity, w=2 or its vicinity For example, LiNi x Mn y Co z O w (x, y, z and w are, for example, x=0.5 or its vicinity, y=0.3 or its vicinity, z=0 .2 or nearby, w=2 or nearby) can be used. iNi x Mn y Co z O w (x, y, z and w are, for example, x=0.6 or (y=0.2 or its vicinity, z=0.2 or its vicinity, w=2 or its vicinity) For example, LiNi x Mn y Co z O w (x, y, z and For example, w is x=0.4 or its vicinity, y=0.4 or its vicinity, z=0.2 or nearby, w=2 or nearby) can be used.
[0054] The neighborhood is, for example, a value greater than 0.9 times and less than 1.1 times the value.
[0055] Some of the transition metals and lithium in the crystal grain 101 are replaced with Fe, Co, Ni, Cr, Al, and Mg. Materials in which one or more elements selected from the above are substituted, and crystal grains 101 are made of Fe, Co, Ni, C The crystal grains 101 are made of a material doped with one or more elements selected from R, Al, Mg, etc. may be used.
[0056] As an example of a material with a spinel-type crystal structure, the composite oxide represented by LiM2O4 is It is preferable to have Mn as the element M. For example, LiMnO In addition, by having Ni in addition to Mn as the element M, This is preferable because it may improve the discharge voltage of the secondary battery and improve the energy density. Lithium-containing materials with a spinel-type crystal structure containing manganese, such as iMn2O4, Amount of lithium nickel oxide (LiNiO2 or LiNi 1-x M x O2 (M=Co, Al, etc.) ) is preferably mixed, since it is possible to improve the characteristics of the secondary battery.
[0057] For example, the average particle size of the primary particles of the positive electrode active material is 1 nm or more and 100 μm or less. It is preferable that the thickness is 50 nm or more and 50 μm or less, and more preferable that the thickness is 1 μm or more and 30 μm or less. It is more preferable that the specific surface area is less than 1 m 2 / g or more 20m 2 / g or less The average particle size of the secondary particles is preferably 5 μm or more and 50 μm or less. The average particle size is measured by scanning electron microscope (SEM). Observation using a TEM (transmission electron microscope) or a laser diffraction / scattering method The specific surface area can be measured by a particle size distribution meter or the like. It can be measured.
[0058] A conductive material such as a carbon layer may be provided on the surface of the positive electrode active material. By providing a carbon layer on the positive electrode active material, the conductivity of the electrode can be improved. The coating is formed by mixing carbohydrates such as glucose during the firing of the positive electrode active material. In addition, graphene, multi-graphene, graphene oxide ( GO: Graphene Oxide) or RGO (Reduced Graphene Here, RGO can be, for example, graphene oxide (GO). ) is reduced.
[0059] A layer containing one or more of an oxide and a fluoride may be provided on the surface of the positive electrode active material. The oxide may have a different composition from that of the crystal grains 101. Also, the oxide may have the same composition as that of the crystal grains 101. It may have.
[0060] For example, a polyanion-based positive electrode material containing oxygen, element X, metal A, and metal M may be used. The metal M can be Fe, Mn, Co, Ni, Ti, V, or N. b or more, metal A is one or more of Li, Na, and Mg, and element X is S, P, Mo, It is one or more of W, As, and Si.
[0061] Examples of materials having an olivine-type crystal structure include composite materials (general formula LiMPO4 (M is , Fe(II), Mn(II), Co(II), Ni(II) Representative examples of the general formula LiMPO4 include LiFePO4, LiNiPO4, and Li iCoPO4, LiMnPO4, LiFe a Ni b PO4, LiFe a Co b PO4, L iFe a Mn b PO4, LiNi a Co b PO4, LiNi a Mn b PO4(a+b is 1 Below, 0 <a<1、0<b<1)、LiFe c Ni d Co e PO4, LiFe c Nid M n e PO4, LiNi c Co d Mn e PO4 (where c + d + e is 1 or less, 0 < c < 1, 0 < d < 1, 0 < e < 1), LiFe f Ni g Co h Mn i PO4 (where f + g + h + i is 1 or less, 0 < f < 1, 0 < g < 1, 0 < h < 1, 0 < i < 1), etc., lithium compounds can be used for this purpose.
[0062] In particular, LiFePO4 satisfies well the requirements for a cathode active material, such as safety, stability, high capacity density, and the presence of lithium ions that can be extracted during initial oxidation (charging). Therefore, it is preferable.
[0063] The cathode active material having an olivine-type crystal structure preferably has an average particle diameter of primary particles of 1 nm or more and 20 μm or less, more preferably 10 nm or more and 5 μm or less and even more preferably 50 nm or more and 2 μm or less. Also, the specific surface area is preferably 1 m 2 / g or more and 20 m 2 / g or less. Also, the average particle diameter of secondary particles is preferably 5 μm or more and 5 0 μm or less.
[0064] Also, composite materials such as the general formula Li (2-j) MSiO4 (where M is one or more of Fe(II), Mn(II), Co(I I), Ni(II), 0 ≤ j ≤ 2), etc., can be used. The general formula Li (2-j) MSiO4 representative examples include Li (2-j) FeSiO4, Li (2- j) NiSiO4, Li (2-j)CoSiO4, Li (2-j) MnSiO4, Li ( 2-j) Fe k Ni l SiO4, Li (2-j) Fe k Co l SiO4, Li (2-j) Fe k Mn l SiO4, Li (2-j) Ni k Co l SiO4, Li (2-j) Ni k M n l SiO4 (k + l is 1 or less, 0 < k < 1, 0 < l < 1), Li (2-j) Fe m Ni n Co q SiO4, Li (2-j) Fe m Ni n Mn q SiO4, Li (2-j) Ni m Co n Mn q SiO4 (m + n + q is 1 or less, 0 < m < 1, 0 < n < 1, 0 < q < 1), Li (2-j) Fe r Ni s Co t Mn u SiO4 (r + s + t + u is 1 or less, 0 < r < 1, 0 < s < 1, 0 < t < 1, 0 < u < 1), etc. exist.
[0065] Also, A x M2(XO4)3 (A = Li, Na, Mg, M = Fe, Mn, Ti, V, Nb , X = S, P, Mo, W, As, Si) can be used with a general formula of a NASICON-type compound. Examples of the NASICON-type compound include Fe2(MnO4)3, Fe2(SO4)3, Li3Fe2(PO4)3, etc. Also, as the crystal grains 101, Li2MPO4F, L The compounds represented by the general formula i2MP2O7 and Li5MO4 (M=Fe, Mn) are used. This can be done.
[0066] The crystal grains 101 are made of perovskite-type fluorides such as NaFeF3 and FeF3, T Metal chalcogenides (sulfides, selenides, tellurides) such as iS2 and MoS2, LiM Oxides with an inverse spinel crystal structure such as VO4, vanadium oxides (V2O5, V6 O 13 Materials such as manganese oxides and organic sulfur compounds can be used. Cut.
[0067] The crystal grains 101 are formed of a material represented by the general formula LiMBO3 (wherein M is Fe(II), Mn(II), Borate-based positive electrode materials represented by one or more of Co(II) can be used.
[0068] In addition, for example, a solid solution of a combination of multiple composite oxides may be used as the crystal grains 101. It is possible. a O2 and Li2M b Solid solution of O3 (M a , M b are each independently a transition metal (One or more selected from the group consisting of) are sometimes called lithium excess oxides. For example, LiNi x Mn y Co z Crystallize a solid solution of O2 (x, y, z>0, x+y+z=1) and Li2MnO3 It can be used as the grain 101.
[0069] In addition, as the crystal grain 101, the composition formula Li a Mn b M c O d Lithium ion can be expressed as In this case, the element M is any element other than lithium or manganese. It is preferable to use a metal element selected from the group consisting of silicon and phosphorus, and nickel is preferably used. It is more preferable to measure the entire particle of the lithium manganese composite oxide. When the voltage is applied <a / (b+c)<2、かつc>, the value is 0.0 and 0.26≦(b+c) / d<0.5. In order to realize high capacity, it is preferable that the crystal structure is The lithium manganese composite oxide has regions with different crystal orientations or oxygen contents. In order to obtain such a lithium manganese composite oxide, it is preferable that, for example, 1.6≦ It is preferable that a≦1.848, 0.19≦c / b≦0.935, and 2.5≦d≦3. In addition, Li 1.68 Mn 0.8062 Ni 0.318 The formula for the compound is O3. It is particularly preferable to use lithium manganese composite oxide. 1. 68 Mn 0.8062 Ni 0.318 Lithium manganese composite with the formula O3 The oxide is the ratio (molar ratio) of the amount of raw materials, Li2CO3:MnCO3:NiO=0 Lithium manganese oxide composite formed by mixing 0.84:0.8062:0.318 Therefore, the lithium manganese composite oxide has the composition formula Li 1.68 Mn 0.80 62 Ni 0.318 It is represented by O3, but the composition can deviate from this.
[0070] The composition of metals, silicon, phosphorus, etc. of the entire lithium manganese composite oxide particle is, for example, For example, it can be measured using an ICP-MS (inductively coupled plasma mass spectrometer). The oxygen composition of the entire particle of the lithium manganese oxide composite was measured using, for example, EDX (energy dispersive X-ray diffraction). It is also possible to measure the melting point by using ICP-MS analysis. This can be determined by using degassing analysis and valence evaluation from XAFS (X-ray absorption fine structure) analysis. The lithium manganese composite oxide is a material that contains at least lithium and manganese. The term refers to oxides of chromium, cobalt, aluminum, nickel, iron, magnesium, molybdenum, etc. Butan, zinc, indium, gallium, copper, titanium, niobium, silicon, and phosphorus, etc. It may contain at least one element selected from the group consisting of:
[0071] In addition, sodium, potassium, and strontium are used as carrier ions instead of lithium. For example, a layered oxide containing sodium may be used. It is possible.
[0072] Examples of materials containing sodium include NaFeO2 and Na 2 / 3 [Fe 1 / 2 Mn1 / 2 ]O2, Na 2 / 3 [Ni 1 / 3 Mn 2 / 3 ]O2, Na2Fe2(SO4)3, N a3V2(PO4)3, Na2FePO4F, NaVPO4F, NaMPO4 (M is F e(II), Mn(II), Co(II), Ni(II), Na2FePO4 F, sodium-containing oxides such as Na4Co3(PO4)2P2O7 are used as the positive electrode active material. It can be used.
[0073] In addition, lithium-containing metal sulfides can be used as the positive electrode active material. For example, Li 2TiS3, Li3NbS4, etc.
[0074] So far, the positive electrode active material particle 100 has crystal grains 101 and crystal grain boundaries 103. However, one embodiment of the present invention is not limited thereto. The particle of material 100 may have a region 107. The region 107 may be, for example, a grain 101. The region 107 may be provided so as to be in contact with at least a portion of the graphene compound. or a decomposition product of lithium or the electrolyte. When the region 107 is a coating containing carbon, the positive electrode active material particles This can increase the electrical conductivity between the positive electrode active material particles 100 and between the positive electrode active material particles 100 and the current collector. Also, when the region 107 is a coating having lithium or a decomposition product of the electrolyte, the electrolyte and This can suppress excessive reaction, and improve the cycle characteristics when used in a secondary battery.
[0075] If the particle diameter of the positive electrode active material particles 100 is too large, it becomes difficult for lithium to diffuse. If it is too high, the bulk density of the electrode will decrease, and the reaction with the electrolyte will proceed excessively. Therefore, the particle size is preferably 1 μm or more and 100 μm or less, and more preferably 10 μm or more and 70 μm or less. It is more preferable that the particle size is equal to or smaller than 50 μm. This refers to the value (D50).
[0076] [Method of producing positive electrode active material] A method for producing a positive electrode active material particle 100 having crystal grains 101 and crystal grain boundaries 103 is described using FIG. The crystal grains 101 are made of a composite oxide containing lithium, a transition metal (M) and oxygen. The grain boundary 103 contains magnesium, fluorine, and oxygen.
[0077] First, starting materials are prepared (step S11). Specifically, a lithium source, a transition metal (M The ammonium phosphate source, magnesium source and fluorine source are each weighed out.
[0078] Examples of lithium sources include lithium carbonate, lithium fluoride, lithium hydroxide, and lithium oxide. etc. can be used.
[0079] As a source of transition metal (M), for example, cobalt compounds, nickel compounds, manganese compounds, iron compounds, Compounds, vanadium compounds, titanium compounds, molybdenum compounds, zinc compounds, indium Compounds such as gallium compounds, copper compounds, and niobium compounds can be used.
[0080] Examples of the cobalt compounds include cobalt oxide, cobalt hydroxide, and cobalt oxyhydroxide. One or more of cobalt carbonate, cobalt oxalate, cobalt sulfate, and the like can be used.
[0081] Nickel compounds include, for example, nickel oxide, nickel hydroxide, nickel carbonate, and nickel chloride. Nickel, nickel bromide, nickel iodide, nickel sulfate, nickel nitrate, nickel formate, etc. More than one may be used.
[0082] Examples of manganese compounds include manganese oxide, manganese hydroxide, manganese carbonate, and manganese chloride. One or more of manganese, manganese iodide, manganese sulfate, and manganese nitrate may be used.
[0083] Examples of iron compounds include iron fluoride, iron chloride, iron bromide, iron iodide, iron sulfate, iron phosphate, and sulphur. One or more of iron phosphate, iron acetate, and the like can be used.
[0084] Examples of vanadium compounds include vanadium oxide, vanadium hydroxide, vanadium chloride, One or more vanadium sulfates may be used.
[0085] Titanium compounds include, for example, titanium fluoride, titanium chloride, titanium bromide, titanium iodide, titanium oxide, One or more of titanium oxide, titanium sulfide, titanium sulfate, etc. can be used.
[0086] Examples of molybdenum compounds include molybdenum oxide, diammonium molybdate, phosphorus molybdate, and the like. One or more of the above may be used, such as butadiene acid.
[0087] Zinc compounds include, for example, zinc oxide, zinc hydroxide, zinc nitrate, zinc sulfate, zinc chloride, and zinc carbonate. One or more of these can be used, such as zinc.
[0088] Examples of indium compounds include indium chloride, indium sulfate, indium nitrate, and indium acid. Indium oxide, indium hydroxide, or the like can be used.
[0089] As the gallium compound, for example, one or more of gallium chloride, gallium fluoride, etc. may be used. can.
[0090] As the copper compound, for example, one or more of copper sulfate, copper chloride, copper nitrate, and the like can be used.
[0091] Examples of niobium compounds include niobium oxide, niobium chloride, niobium oxide sulfate, and niobium fluoride. One or more of the following may be used.
[0092] The magnesium source may be, for example, magnesium oxide, magnesium fluoride, magnesium hydroxide, etc. One or more of the above may be used, such as sodium carbonate, magnesium carbonate, etc.
[0093] As the fluorine source, for example, one or more of lithium fluoride, magnesium fluoride, etc. may be used. In other words, lithium fluoride can be used as both a lithium source and a fluorine source. Magnesium fluoride can be used both as a magnesium source and as a fluorine source. can.
[0094] In addition, when the crystal grain 101 contains a metal other than the transition metal in addition to the transition metal (M), Weigh out the source of metal other than the transition metal. When the source of metal other than the transition metal is aluminum, As the metal source, for example, an aluminum compound can be used. Aluminum oxide, aluminum hydroxide, aluminum carbonate, aluminum chloride, One or more of aluminum iodide, aluminum sulfate, aluminum nitrate, etc. can be used. Cut.
[0095] The ratio of the number of atoms of the raw transition metal (M) and magnesium is explained. The ratio m of the number of atoms of magnesium, Mg(r), to the number of atoms, M(r), is 0.0050. More than 0.050, that is, the number of transition metal atoms M(r): the number of magnesium atoms Mg(r )=1.0:m, 0.0050≦m≦0.050 is preferable. The ratio m of the number of magnesium atoms to the number of atoms of is 0.010 or close to 1.0% By setting the above-mentioned atomic ratio, the grain boundary 103 is preferably filled with magnesium. It is possible to efficiently produce a positive electrode active material containing lithium. In this case, the total number of transition metal atoms of multiple types is used for the number of transition metal atoms M(r) mentioned above. It is also possible to calculate
[0096] The neighborhood is, for example, a value greater than 0.9 times and less than 1.1 times the value.
[0097] The ratio of the number of magnesium atoms in the raw material to the number of fluorine atoms is explained below. The ratio n of the number of fluorine atoms F(r) to the number Mg(r) is 1.50 or more and 4.0 or less. The number of magnesium atoms Mg(r) is the number of fluorine atoms F(r) = 1.0: n is 1 It is preferable that n is 50≦n≦4.0. Furthermore, the ratio of fluorine atoms to the number of magnesium atoms is 50≦n≦4.0. The ratio of the numbers, n, is 2.0 or close to 2.0, that is, the number of magnesium atoms, Mg(r): the number of fluorine atoms. It is more preferable that the number of atoms F(r) is 1.0:2.0 or close to that. By setting the ratio to 103, magnesium and fluorine can be efficiently segregated to the grain boundary 103. can.
[0098] The atomic ratio of the raw material transition metal, magnesium and fluorine can be expressed by the following formula 1. Here, m is the ratio of the number of magnesium atoms, Mg(r), to the number of transition metal atoms, M(r). As mentioned above, 0.0050≦m≦0.050 is preferable, and m=0.0 n is the number of fluorine atoms relative to the number of magnesium atoms Mg(r), and is preferably about 10. As mentioned above, 1.50≦n≦4.0 is preferable, and more preferably, For this, n=2.0 or its vicinity is preferable.
[0099]
number
[0100] An example of the ratio of raw materials when LiCoO2 is produced as the positive electrode active material particles is shown below. The ratio m of the number of magnesium atoms to the number of cobalt atoms is 0.010. The ratio of the number of fluorine atoms to the number of fluorine atoms is set to 2.0. The ratio of the numbers of atoms of barium, magnesium, and fluorine is Co:Mg:F=1.0:0.010. :0.020.
[0101] The atomic ratio of the raw materials and the composition of the positive electrode active material particles 100 obtained by synthesis are This may not be the case.
[0102] The molar ratio of the lithium compound and transition metal (M) compound in the raw materials is determined based on the assumed crystal grain size. In addition, for example, the molar ratio of the lithium compound in the raw material is On the other hand, if the lithium content of the resulting crystal grains is low, the molar ratio of the lithium compound in the raw material may be increased.
[0103] Next, the weighed starting materials are mixed (step S12). A rice mill or the like can be used.
[0104] Next, the material mixed in step S12 is subjected to a first heating (step S13). Heating is preferably carried out at a temperature of 800°C or higher and 1050°C or lower, and more preferably at a temperature of 900°C or higher and 1000°C or lower. It is more preferable to carry out the heating for a period of time ranging from 2 hours to 20 hours. The first heating is preferably carried out in an oxygen-containing atmosphere, for example in a dry air atmosphere. It is preferable to carry out the process in the following manner.
[0105] The first heating in step S13 converts the lithium and transition metal (M) contained in the crystal grains 101 into In addition, the first heating step can synthesize a complex oxide containing the The magnesium and fluorine are partly deposited on the surface of a complex oxide containing lithium and a transition metal (M). However, at this point, other parts of magnesium and fluorine are in transition with lithium. It is in a state of being solid-dissolved in a complex oxide containing a metal (M).
[0106] Next, the material heated in step S13 is cooled to room temperature (step S14). By subjecting the synthesized material to a crushing process, the particle size of the positive electrode active material particles 100 can be reduced. This is preferable.
[0107] Next, the material cooled in step S14 is subjected to a second heating (step S15). Heating should be performed for a holding time of 100 hours or less at the specified temperature, and should be performed for 1 hour to 70 hours. More preferably, the reaction is carried out for 2 to 50 hours, and more preferably for 2 to 50 hours. It is more preferable to perform the treatment for 2 to 35 hours. 00°C or less is preferable, 700°C to 1000°C is more preferable, and about 800°C is the most preferable. It is more preferable that the second heating is performed in an atmosphere containing oxygen. For example, drying It is preferable to carry out the treatment in an air atmosphere.
[0108] By performing the second heating in step S15, magnesium and fluorine contained in the starting material are , it can promote segregation to the grain boundaries.
[0109] Finally, the material heated in S15 is cooled to room temperature and collected (step S16) to activate the positive electrode. A substance particle 100 can be obtained.
[0110] As mentioned above, by mixing the magnesium source and the fluorine source as starting materials, the grain boundaries A positive electrode active material having magnesium oxide in 103 can be efficiently produced.
[0111] In addition, by mixing a magnesium source and a fluorine source as starting materials, the grain boundaries 10 3. Magnesium may be more likely to segregate.
[0112] The oxygen that bonds with magnesium is replaced with fluorine, and the surroundings of the replaced fluorine Magnesium may become more mobile in
[0113] Furthermore, adding magnesium fluoride to magnesium oxide may lower the melting point. The lowering of the melting point makes it easier for atoms to move during heat treatment.
[0114] Also, fluorine has a higher electronegativity than oxygen. Therefore, magnesium oxide Even in stable compounds, the addition of fluorine causes charge imbalance, resulting in magnesium This can weaken the bond between oxygen and oxygen.
[0115] For these reasons, by mixing a magnesium source and a fluorine source as starting materials, , magnesium becomes more mobile and tends to segregate at the grain boundaries 103. There are cases.
[0116] By using the positive electrode active material particles 100 described in this embodiment, deterioration is reduced and safety is improved. This embodiment mode may be appropriately combined with any of the other embodiment modes. It can be used.
[0117] (Embodiment 2) In this embodiment, a secondary battery having the positive electrode active material particles 100 described in the previous embodiment is Examples of materials that can be used will be described. In this embodiment, the positive electrode, the negative electrode, and the The following description will be given taking as an example a secondary battery in which the electrolyte is enclosed in an exterior body.
[0118] [Positive electrode] The positive electrode has a positive electrode active material layer and a positive electrode current collector.
[0119] <Cathode active material layer> The positive electrode active material layer includes positive electrode active material particles. The positive electrode active material layer also includes a conductive additive and a biocompatible material. The semiconductor device may have a fin.
[0120] The positive electrode active material particles are the positive electrode active material particles 100 described in the previous embodiment. By using the positive electrode active material particles 100 described in the above embodiment, deterioration is reduced. Therefore, it is possible to provide a highly safe secondary battery.
[0121] As the conductive assistant, a carbon material, a metal material, a conductive ceramic material, or the like can be used. In addition, a fibrous material may be used as the conductive assistant. The content of the electrical auxiliary agent is preferably 1 wt% or more and 10 wt% or less, and more preferably 1 wt% or more and 5 wt% or less. is more preferred.
[0122] The conductive additive can form an electrically conductive network in the electrode. This makes it possible to maintain the electrical conduction path between the positive electrode active material particles. By adding an electrical auxiliary agent, it is possible to realize an active material layer having high electrical conductivity. .
[0123] Examples of the conductive assistant include natural graphite, artificial graphite such as mesocarbon microbeads, and carbon fibers. Examples of carbon fibers that can be used include mesophase pitch carbon fibers. In addition, carbon fibers such as isotropic pitch-based carbon fibers can be used. Carbon nanofibers and carbon nanotubes can be used. The tube can be produced by, for example, a vapor phase growth method. For example, carbon black (acetylene black (AB) etc.), graphite particles Carbon materials such as copper, nickel, and graphene can be used. Nickel, aluminum, silver, gold and other metal powders, metal fibers, conductive ceramic materials, etc. It can be used.
[0124] In addition, a graphene compound may be used as the conductive assistant.
[0125] Graphene compounds have excellent electrical properties, such as high electrical conductivity, as well as high flexibility and In addition, graphene may have excellent physical properties such as high mechanical strength. The compound has a planar shape. Graphene compounds enable surface contact with low contact resistance. In addition, even if the material is thin, it can have very high conductivity, and a small amount of the material can be used to efficiently conduct electricity within the active material layer. Therefore, the graphene compound can be used as a conductive additive. This is preferable because it is possible to increase the contact area between the active material and the conductive assistant. In this case, the graphene compound is preferably a graphene compound having a low electrical resistance. For example, graphene or multi-graphene or reduced graphene O It is particularly preferred to use RGO oxide. This refers to a compound obtained by reducing graphene (GO: Graphene Oxide).
[0126] When using active material particles with a small particle size, for example, active material particles with a particle size of 1 μm or less, The specific surface area of the active material particles is large, and more conductive paths are required to connect the active material particles. The amount of the conductive additive increases, and the amount of the active material carried may decrease relatively. If the amount of the conductive additive decreases, the capacity of the secondary battery decreases. When graphene compounds are used, they can efficiently form conductive paths even in small amounts. This is particularly preferable because it is possible to avoid reducing the amount of the active material carried.
[0127] In the following, as an example, a graphene compound is used as a conductive assistant in the active material layer 200. An example of the cross-sectional structure will be described.
[0128] 4A shows a vertical cross-sectional view of the active material layer 200. The active material layer 200 is made of granular positive electrode active material. Particles 100, a graphene compound 201 as a conductive assistant, a binder (not shown), Here, the graphene compound 201 may be, for example, graphene or multigraphene. Here, the graphene compound 201 preferably has a sheet shape. In addition, the graphene compound 201 may be a multi-graphene or (and) A plurality of graphenes may be partially overlapped to form a sheet.
[0129] In the vertical cross section of the active material layer 200, as shown in FIG. In FIG. 4(A), the sheet-like graphene compound 201 is dispersed almost uniformly. The graphene compound 201 is shown in bold in schematic form, but in reality it is a single or multiple layer of carbon molecules. The graphene compounds 201 are thin films having a thickness of 100 nm. The positive electrode active material particles 100 are wrapped or covered with the positive electrode active material particles 100. They are formed to adhere to the surface, so that they are in surface contact with each other.
[0130] Here, a plurality of graphene compounds are bonded to each other to form a mesh-like graphene compound. The graphene compound is then bonded to the graphene sheet (hereinafter referred to as a graphene compound net or a graphene net). When the active material is covered with a graphene net, the graphene net can bond the active material to each other. It can also function as a binder to bind the material together. This allows the amount of binder to be reduced. Since it is possible to reduce the ratio of active material to the electrode volume or weight, or it is not necessary to use In other words, the capacity of the power storage device can be increased.
[0131] Here, graphene oxide is used as the graphene compound 201, and is mixed with an active material to form an active material. After the layer that will become the layer 200 is formed, it is preferable to reduce it. By using graphene oxide, which has extremely high dispersibility in polar solvents, The mixture 201 can be dispersed approximately uniformly inside the active material layer 200. The solvent is removed by evaporation from the dispersion medium containing the dispersed graphene oxide, and the graphene oxide is reduced. Therefore, the graphene compounds 201 remaining in the active material layer 200 are partially overlapped with each other. By dispersing the particles so that they are in surface contact with each other, a three-dimensional conductive path can be formed. The reduction of graphene oxide may be performed, for example, by heat treatment or by using a reducing agent. This is also possible.
[0132] Therefore, unlike granular conductive additives such as acetylene black, which come into point contact with the active material, graphite Since the compound 201 enables surface contact with low contact resistance, it is more effective than ordinary conductive additives. The amount of the granular positive electrode active material particles 100 and the graphene compound 201 is smaller than that of the graphene compound 201. Therefore, the ratio of the positive electrode active material particles 100 in the active material layer 200 can be increased. This makes it possible to increase the discharge capacity of the power storage device.
[0133] Examples of binders include styrene-butadiene rubber (SBR) and styrene-isoprene. Acrylonitrile-styrene rubber, butadiene rubber, ethylene-styrene rubber, acrylonitrile-butadiene rubber, butadiene rubber, It is preferable to use a rubber material such as a propylene-diene copolymer. Fluorine rubber can be used.
[0134] As the binder, it is preferable to use, for example, a water-soluble polymer. As the molecule, for example, polysaccharides can be used. CMC, methyl cellulose, ethyl cellulose, hydroxypropyl cellulose Cellulose derivatives such as cellulose, diacetyl cellulose, regenerated cellulose, and starch These water-soluble polymers can be used in combination with the above-mentioned rubber materials. It is even better if there is a
[0135] Alternatively, the binder may be polystyrene, polymethyl acrylate, or polymethyl methacrylate. Polymethylmethacrylate (PMMA), Sodium polyacrylate, Polyvinyl alcohol (PVA), Poly Ethylene oxide (PEO), polypropylene oxide, polyimide, polyvinyl chloride, Polytetrafluoroethylene, polyethylene, polypropylene, polyisobutylene, poly Ethylene terephthalate, nylon, polyvinylidene fluoride (PVDF), polyacrylo Nitrile (PAN), Ethylene Propylene Diene Polymer, Polyvinyl Acetate, Nitrocel It is preferable to use a material such as loin.
[0136] The binder may be used in combination of two or more of the above.
[0137] For example, a material having a particularly excellent viscosity adjusting effect may be used in combination with other materials. For example, rubber materials have excellent adhesive strength and elasticity, but it is difficult to adjust the viscosity when mixed with a solvent. In such cases, for example, it is possible to mix the material with a particularly excellent viscosity adjusting effect. As a material having a particularly excellent viscosity adjusting effect, for example, a water-soluble polymer is preferably used. In addition, examples of water-soluble polymers that are particularly effective in adjusting viscosity include the aforementioned polysaccharides, such as calcium carbonate. Carboxymethylcellulose (CMC), methylcellulose, ethylcellulose, hydroxy Cellulose derivatives such as propyl cellulose, diacetyl cellulose, and regenerated cellulose For example, starch or starch can be used.
[0138] In addition, cellulose derivatives such as carboxymethyl cellulose are, for example, carboxymethyl The solubility of cellulose increases when it is converted into a salt such as sodium salt or ammonium salt. It is easy to exert its effect as a viscosity adjuster. The higher the solubility, the easier it is to make the electrode slurry. In the preparation of the electrode, the dispersibility of the electrode with the active material and other components can be improved. In this regard, the cellulose and cellulose derivatives used as the binder for the electrodes are as follows: These salts are also included.
[0139] Water-soluble polymers stabilize the viscosity by dissolving in water, and also serve as active materials and binders. Other materials to be combined, such as styrene butadiene rubber, are stable in aqueous solution. In addition, since it has a functional group, it is easy to stably adsorb on the surface of the active material. It is expected that cellulose derivatives such as carboxymethyl cellulose, for example, For example, many materials have functional groups such as hydroxyl groups and carboxyl groups. It is expected that the polymers will interact with each other and widely cover the surface of the active material.
[0140] When the binder that covers or contacts the surface of the active material forms a film, it is called a passive film. It is expected that the passive film will also play a role in preventing the decomposition of the electrolyte. A film with no electrical conductivity or extremely low electrical conductivity is used. For example, When a dynamic membrane is formed, it is possible to suppress the decomposition of the electrolyte at the battery reaction potential. In addition, the passive film suppresses electrical conductivity while allowing lithium ions to conduct. And even more desirable.
[0141] <Positive electrode current collector> The positive electrode current collector may be made of metals such as stainless steel, gold, platinum, aluminum, titanium, or the like. In addition, the material used for the positive electrode current collector can be an alloy of these materials, which has high electrical conductivity. It is preferable that the material does not dissolve at the potential of the positive electrode. Aluminum alloys containing elements such as indium and molybdenum that improve heat resistance are used. It can also be formed from a metal element that reacts with silicon to form a silicide. Metal elements that react with silicon to form silicide include zirconium, titanium, and Tantalum, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten , cobalt, nickel, etc. Current collectors are available in foil, plate (sheet), mesh, punched The current collector may be in the form of a metal, an expanded metal, or the like. It is advisable to use one with a thickness of 5 μm or more and 30 μm or less.
[0142] [Negative electrode] The negative electrode has a negative electrode active material layer and a negative electrode current collector. The negative electrode active material layer contains a conductive assistant and and a binder.
[0143] <Negative electrode active material> As the negative electrode active material, for example, an alloy-based material or a carbon-based material can be used.
[0144] As a negative electrode active material, it is possible to carry out charge / discharge reactions by alloying / de-alloying reactions with lithium. For example, silicon, tin, gallium, aluminum, and Rumanium, lead, antimony, bismuth, silver, zinc, cadmium, indium, etc. Materials containing at least one of these elements can be used. These elements have a large capacity compared to carbon. Silicon has a high theoretical capacity of 4200mAh / g. It is preferable to use silicon. Compounds containing these elements may also be used. For example, SiO, Mg2Si, Mg2Ge, SnO, SnO2, Mg2Sn, SnS2, V 2Sn3, FeSn2, CoSn2, Ni3Sn2, Cu6Sn5, Ag3Sn, Ag3 Sb, Ni2MnSb, CeSb3, LaSn3, La3Co2Sn7, CoSb3, I nSb, SbSn, etc. Here, the charge / discharge reaction occurs due to alloying / dealloying reactions with lithium. Elements capable of undergoing a reaction and compounds containing such elements are sometimes called alloy materials. do.
[0145] In this specification, SiO refers to, for example, silicon monoxide. Alternatively, SiO xHere, x preferably has a value of 1 or close to 1. For example, For example, x is preferably 0.2 or more and 1.5 or less, and more preferably 0.3 or more and 1.2 or less.
[0146] Carbon-based materials include graphite, graphitizable carbon (soft carbon), and non-graphitizable carbon (hard carbon). Carbon nanotubes, graphene, carbon black, etc. may be used. .
[0147] Examples of graphite include artificial graphite and natural graphite. Examples of artificial graphite include mesophase graphite. Carbon microbeads (MCMB), coke-based artificial graphite, pitch-based artificial graphite, etc. Here, as the artificial graphite, spherical graphite having a spherical shape can be used. For example, the MCMB may have a spherical shape, which is preferred. It is relatively easy to reduce the particle size, which may be preferable. Examples of the graphite include flake graphite and spherical natural graphite.
[0148] When lithium ions are inserted into graphite (when lithium-graphite intercalation compounds are formed), It has a low potential similar to that of lithium metal (0.05V to 0.3V vs. Li / L i + This allows the lithium-ion secondary battery to exhibit a high operating voltage. In addition, graphite has a relatively high capacitance per unit volume, a relatively small volume expansion, and is inexpensive. However, lithium ions are preferred because they have the advantage of being safer than metallic lithium.
[0149] In addition, titanium dioxide (TiO2) and lithium titanium oxide (Li4T i5O 12 ), lithium-graphite intercalation compound (Li xC6), niobium pentoxide (Nb2O5) Oxides such as tungsten oxide (WO2) and molybdenum oxide (MoO2) can be used. can.
[0150] In addition, the negative electrode active material is a composite nitride of lithium and transition metals, which has a Li3N structure. Li 3-x M x N (M=Co, Ni, Cu) can be used. For example, Li 2.6 Co 0.4 N3 has a large charge / discharge capacity (900mAh / g, 1890mAh / cm 3 ) And preferable.
[0151] When a composite nitride of lithium and transition metals is used, the negative electrode active material contains lithium ions, The positive electrode active material is made of V2O5, Cr3O8, etc., which do not contain lithium ions. It is preferable that the positive electrode active material contains lithium ions. The lithium ions contained in the positive electrode active material are first removed to form the negative electrode active material. A complex nitride of lithium and a transition metal can be used.
[0152] In addition, a material that undergoes a conversion reaction can also be used as the negative electrode active material. For example, Lithium oxide (LiO), cobalt oxide (CoO), nickel oxide (NiO), iron oxide (FeO), etc. A transition metal oxide that does not form an alloy with the negative electrode active material may be used. Further materials that are produced include Fe2O3, CuO, Cu2O, RuO2, Cr2O3, etc. oxide, CoS 0.89 , NiS, CuS and other sulfides, Zn3N2, Cu3N, Ge3 Nitrides such as N4, phosphides such as NiP2, FeP2, CoP3, FeF3, BiF3, etc. Fluoride is one example.
[0153] The conductive assistant and binder that can be contained in the negative electrode active material layer are the same as those that can be contained in the positive electrode active material layer. The conductive additive and binder may be the same as those that can be used.
[0154] <Negative electrode current collector> The negative electrode current collector can be made of the same material as the positive electrode current collector. It is preferable to use a material that does not alloy with carrier ions such as lithium.
[0155] [Electrolyte] The electrolytic solution contains a solvent and an electrolyte. The solvent for the electrolytic solution is preferably an aprotic organic solvent. Preferable examples include ethylene carbonate (EC), propylene carbonate (PC), Ethylene carbonate, chloroethylene carbonate, vinylene carbonate, gamma-butyro Lactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate DEC, Ethyl methyl carbonate (EMC), Methyl formate, Methyl acetate, Ethyl acetate ethyl, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1,3-dioxane, 1,4-dioxane, dimethoxyethane (DME), dimethylsulfate phthalocyanine, diethyl ether, methyl diglyme, acetonitrile, benzonitrile, One of tetrahydrofuran, sulfolane, sultone, etc., or two or more of these can be used in any combination and ratio.
[0156] In addition, a phosphate ester compound having fluorine, which is flame-retardant as a solvent for the electrolyte, or By using a fluorine-containing carbonate compound, it is possible to prevent explosion or fire of the storage device. Examples of fluorine-containing phosphate ester compounds include tris(2,2, 2-trifluoroethyl)phosphate (TFEP) and other fluorine-containing carbonates. Examples of ester compounds include bis(2,2,2-trifluoroethyl)carbonate. (TFEC), etc.
[0157] In addition, by using a polymer material that gels as a solvent for the electrolyte, the resistance to leakage, etc. Safety is improved. In addition, it is possible to make the secondary battery thinner and lighter. Representative examples of materials include silicone gel, acrylic gel, acrylonitrile gel, and poly Ethylene oxide gel, polypropylene oxide gel, fluorine polymer gel etc.
[0158] In addition, a flame-retardant and non-volatile ionic liquid (room-temperature molten salt) is used as the solvent for the electrolyte. By using one or more, the internal temperature of the storage device can be increased due to an internal short circuit or overcharging. Even if the battery is heated, it can prevent the battery from bursting or catching fire. The electrolyte solution is made of cations and anions. Ammonium cations, tertiary sulfonium cations, and quaternary phosphonium cations Aliphatic onium cations such as imidazolium cations and pyridinium cations The aromatic cations are also used as anions in the electrolyte. Anions, monovalent methide anions, fluorosulfonate anions, perfluoroalkyl sulfonic acid anion, tetrafluoroborate anion, perfluoroalkyl borate anion phosphate anion, hexafluorophosphate anion, or perfluoroalkyl phosphat ate anion, etc.
[0159] The electrolyte to be dissolved in the above solvent is, for example, LiPF6, LiClO4, L iAsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO 4. Li2B 10 Cl 10 , Li2B 12 Cl 12 , LiCF3SO3, LiC4F9S O3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2 )2, LiN(C4F9SO2)(CF3SO2), LiN(C2F5SO2)2, etc. One or more of these titanium salts may be used in any combination and ratio. This can be done.
[0160] The electrolyte used in the electricity storage device is free of granular waste and elements other than the constituent elements of the electrolyte (hereinafter simply referred to as " It is preferable to use a highly purified electrolyte solution having a low content of impurities. Specifically, the weight ratio of impurities to the electrolyte is 1% or less, preferably 0.1% or less, more preferably 1% or less. It is preferably 0.01% or less.
[0161] In addition, the electrolyte contains vinylene carbonate, propane sultone (PS), and tert-butyl Benzene (TBB), Fluoroethylene carbonate (FEC), Lithium bis(oxa) Lithium borate (LiBOB), as well as dinitriles such as succinonitrile and adiponitrile compounds, triisopropoxyboroxine (TiPBx), sulfolane, hydrofluoric acid Hydrofluoroethylene (HFE), vinyl acetate (VA), etc. may be added. Concentration of added material For example, the amount may be 0.1 weight% or more and 5 weight% or less of the total solvent. stomach.
[0162] Alternatively, a polymer gel electrolyte may be used in which a polymer is swollen with an electrolytic solution.
[0163] By using a polymer gel electrolyte, safety against leakage etc. is improved. The pond can be made thinner and lighter.
[0164] The polymers that can be gelled include silicone gel, acrylic gel, and acrylonitrile gel. , polyethylene oxide gel, polypropylene oxide gel, fluorine-based polymer As the polymer, for example, polyethylene oxide (PE O), PVDF, and polyacrylic acid Lithonitrile and copolymers containing them can be used. For example, PVDF The copolymer of PVDF and hexafluoropropylene (HFP), PVDF-HFP, is used. The polymer formed may also have a porous shape.
[0165] In addition, instead of an electrolytic solution, a solid electrolyte having an inorganic material such as a sulfide or oxide is used. It is possible to use a solid electrolyte containing a polyethylene oxide (PEO)-based polymer material. When a solid electrolyte is used, the installation of a separator or spacer becomes unnecessary. Since the entire battery can be made solid, there is no risk of leakage, and safety is dramatically improved.
[0166] [Separator] The secondary battery preferably has a separator. The separator may be, for example, a paper. Cellulose-containing fibers, nonwoven fabrics, glass fibers, ceramics, or nanofibers, including those containing cellulose, IRON (polyamide), VINYLON (polyvinyl alcohol fiber), polyester, acrylic The material used must be synthetic fibers such as olefin, polyolefin, and polyurethane. The separator is processed into a bag shape and placed so that it encases either the positive electrode or the negative electrode. It is preferable to do so.
[0167] The separator may be a multi-layer structure. For example, the separator may be made of an organic material such as polypropylene or polyethylene. The material film is made of ceramic, fluorine, polyamide, or a mixture of these materials. The ceramic material can be, for example, aluminum oxide. Examples of the fluorine-based material include fluorine particles, silicon oxide particles, etc. PVDF, polytetrafluoroethylene, etc. can be used. For example, nylon, aramid (meta-aramid, para-aramid), etc. can be used. can.
[0168] Coating with ceramic materials improves oxidation resistance, making it ideal for separators during high-voltage charging and discharging. This suppresses the deterioration of the capacitor and improves the reliability of the secondary battery. By coating the electrode, the separator and the electrode are more easily adhered to each other, improving the output characteristics. Coating polyamide materials, especially aramid, improves heat resistance, which contributes to the safety of secondary batteries. This can improve safety.
[0169] For example, a polypropylene film is coated on both sides with a mixture of aluminum oxide and aramid. Alternatively, aluminum oxide may be applied to the surface of the polypropylene film that comes into contact with the positive electrode. Alternatively, the surface in contact with the negative electrode may be coated with a mixed material of carbon and aramid, and then coated with a fluorine-based material.
[0170] By using a multi-layered separator, the safety of the secondary battery can be ensured even if the overall thickness of the separator is thin. Since the capacity per unit volume of the secondary battery can be increased, the capacity per unit volume of the secondary battery can be increased.
[0171] (Embodiment 3) In this embodiment, a secondary battery having the positive electrode active material particles 100 described in the previous embodiment is An example of the shape will be described. The material used for the secondary battery described in this embodiment is the same as that used in the previous embodiment. The description of the form may be taken into consideration.
[0172] [Coin-type secondary battery] First, an example of a coin-type secondary battery will be described. Figure 5(A) shows a coin-type (single-layer flat type) 5(A) is a cross-sectional view of the secondary battery shown in FIG.
[0173] The coin-type secondary battery 300 has a positive electrode can 301 that also serves as a positive electrode terminal and a negative electrode can 302 that also serves as a negative electrode terminal. 302 is insulated and sealed by a gasket 303 made of polypropylene or the like. The positive electrode 304 is composed of a positive electrode current collector 305 and a positive electrode active material layer 306 provided in contact with the positive electrode current collector 305. The negative electrode 307 is formed by contacting a negative electrode current collector 308. The negative electrode active material layer 309 is formed by bonding the negative electrode active material layer 309 to the negative electrode.
[0174] The positive electrode 304 and the negative electrode 307 used in the coin-type secondary battery 300 are each an active material. The barrier layer need only be formed on one side.
[0175] The positive electrode can 301 and the negative electrode can 302 are made of nickel or aluminum, which is resistant to corrosion by the electrolyte. , titanium, or alloys of these with other metals (e.g. stainless steel In addition, nickel or aluminum can be used to prevent corrosion by the electrolyte. The positive electrode can 301 is for covering the positive electrode 304, and the negative electrode can 302 is for covering the negative electrode 304. 7 and electrically connected to each other.
[0176] The negative electrode 307, the positive electrode 304 and the separator 310 are impregnated with an electrolyte, and then the negative electrode 307, the positive electrode 304 and the separator 310 are impregnated with an electrolyte, as shown in FIG. As shown in FIG. 1, the positive electrode can 301 is placed downward, the positive electrode 304, the separator 310, the negative electrode 307, and the negative The positive electrode can 301 and the negative electrode can 302 are laminated in this order, and the positive electrode can 301 and the negative electrode can 302 are fixed with a gasket 303 interposed therebetween. Then, the laminate is pressed to manufacture a coin-type secondary battery 300.
[0177] By using the positive electrode active material particles 100 described in the previous embodiment for the positive electrode 304, deterioration is prevented. Therefore, the coin-type secondary battery 300 can be made small and highly safe.
[0178] [Cylindrical secondary battery] An example of a cylindrical secondary battery will be described with reference to FIGS. 6(A) to 6(D). The secondary battery 600 is a cylindrical secondary battery 600 shown in FIG. 6(A) and a cross-sectional schematic diagram shown in FIG. As shown in the figure, it has a positive electrode cap (battery lid) 601 on the top surface, and a battery can on the sides and bottom. The positive electrode cap and the battery can (outer can) 602 are made of It is insulated by a gasket (insulating packing) 610.
[0179] Inside a hollow cylindrical battery can 602, a strip-shaped positive electrode 604 and a strip-shaped negative electrode 606 are sandwiched between a separator 6 The battery element is wound around the sensor. The battery can 602 is wound around a turbopin. One end is closed and the other end is open. The battery can 602 is made of nickel, aluminum, titanium, or other material that is resistant to corrosion by the electrolyte. The metals, or their alloys or alloys of these with other metals (e.g., stainless steel, etc.) are used. In addition, to prevent corrosion by the electrolyte, the electrodes are coated with nickel or aluminum. It is preferable to cover the inside of the battery can 602 with a positive electrode, a negative electrode, and a separator. The rotated battery element is sandwiched between a pair of opposing insulating plates 608 and 609. A non-aqueous electrolyte (not shown) is poured into the battery can 602 in which the battery element is provided. The non-aqueous electrolyte may be the same as that used in coin-type secondary batteries.
[0180] The positive and negative electrodes used in cylindrical secondary batteries are wound, so active material is formed on both sides of the current collector. A positive electrode terminal (positive electrode current collecting lead) 603 is connected to the positive electrode 604, and a negative A negative electrode terminal (negative electrode current collecting lead) 607 is connected to the positive electrode 606. The positive terminal 607 may be made of a metal material such as aluminum. 03 is resistance welded to the safety valve mechanism 612, and the negative terminal 607 is resistance welded to the bottom of the battery can 602. The safety valve mechanism 612 is a PTC (Positive Temperature Coefficient) The positive electrode cap 601 is electrically connected to the positive electrode cap 601 via a capacitance 611. The safety valve mechanism 612 is a mechanism for releasing the positive electrode cap 601 when the internal pressure of the battery increases beyond a predetermined threshold. The PTC element 611 cuts off the electrical connection between the positive electrode 604 and the positive electrode 604. It is a thermal resistor element whose resistance increases when the temperature rises, and the amount of current is limited by the increase in resistance. It prevents abnormal heat generation. The PTC element is made of barium titanate (BaTiO3) Semiconductor ceramics and the like can be used.
[0181] As shown in FIG. 6C, a plurality of secondary batteries 600 are arranged between conductive plates 613 and 614. A module 615 may be formed by sandwiching the secondary batteries 600 between them. Alternatively, the elements may be connected in series, or may be connected in parallel and then in series. By configuring a module 615 having a plurality of secondary batteries 600, This allows for the extraction of large amounts of power.
[0182] FIG. 6D is a top view of the module 615. The conductive plate 613 is dotted for clarity. As shown in FIG. 6D, the module 615 is a multiple secondary battery 600. The conductive plate 613 may be provided on the conductive wire 616. In addition, even if a temperature control device 617 is provided between multiple secondary batteries 600, When the secondary battery 600 is overheated, the temperature control device 617 cools the secondary battery. If 600 is too cold, it can be heated by the temperature control device 617. Therefore, the performance of the module 615 is less affected by the outside temperature.
[0183] By using the positive electrode active material particles 100 described in the previous embodiment for the positive electrode 604, deterioration is prevented. Therefore, the cylindrical secondary battery 600 can be made small and highly safe.
[0184] [Structural example of power storage device] Another structural example of the power storage device will be described with reference to FIGS.
[0185] 7(A) and 7(B) are diagrams showing the external appearance of the power storage device. The battery 900 and a secondary battery 913 are attached with a label 910. Furthermore, as shown in FIG. 7B, the power storage device has a terminal 951, a terminal 952, and an The antenna 914 and the antenna 915 .
[0186] The circuit board 900 includes a terminal 911 and a circuit 912. The terminal 911 is connected to a terminal 951. , a terminal 952, an antenna 914, an antenna 915, and a circuit 912. A plurality of terminals 911 are provided, and each of the plurality of terminals 911 is used as a control signal input terminal, a power supply terminal, etc. may also be used.
[0187] The circuit 912 may be provided on the back surface of the circuit board 900. The antenna 915 is not limited to a coil shape, but may be, for example, a wire shape or a plate shape. Planar antenna, aperture antenna, traveling wave antenna, EH antenna, magnetic field antenna, dielectric Alternatively, antenna 914 or antenna 915 may be used. The flat conductor may function as one of the conductors for electric field coupling. In other words, the annulus can be used as one of the two conductors of the capacitor. In this way, the electromagnetic field, the magnetic field, and the like can be detected by the antenna 914 or the antenna 915. Alternatively, power can be exchanged using an electric field.
[0188] The line width of antenna 914 is preferably larger than the line width of antenna 915. This allows the amount of power received by the antenna 914 to be increased.
[0189] The power storage device includes a layer 916 between the antenna 914 and the secondary battery 913 and between the antenna 915 and the secondary battery 913. The layer 916 has a function of blocking an electromagnetic field generated by the secondary battery 913, for example. The material 16 may be, for example, a magnetic material.
[0190] The structure of the electricity storage device is not limited to that shown in FIG.
[0191] For example, as shown in Figs. 8(A-1) and 8(A-2), In the secondary battery 913 shown in FIG. FIG. 8(A-1) is an external view of one side of the pair of surfaces, and FIG. 8(A-2) is an external view of the pair of surfaces. 7(A) and 7(B) are views showing the appearance of the other side of the power storage device. For this, the description of the power storage device in FIGS. 7A and 7B can be referred to as appropriate.
[0192] As shown in FIG. 8(A-1), a layer 916 is sandwiched between one of a pair of surfaces of a secondary battery 913 to form an annular 8(A-2), a retainer 914 is provided on the other of the pair of surfaces of the secondary battery 913. The layer 917 is provided on the secondary battery 913, for example. The layer 917 has a function of blocking the electromagnetic field generated by the magnetic field. Cut.
[0193] By adopting the above structure, the size of both the antenna 914 and the antenna 915 can be increased. It is possible.
[0194] Or, as shown in FIG. 8(B-1) and FIG. 8(B-2), A separate antenna may be provided on each of a pair of opposing surfaces of secondary battery 913. FIG. 8(B-1) is an external view of one side of the pair of surfaces, and FIG. 8(B-2) is an external view of the pair of surfaces. 7(A) and 7(B) are the same parts as those of the power storage device shown in FIG. For this, the description of the power storage device illustrated in FIGS. 7A and 7B can be used as appropriate.
[0195] As shown in FIG. 8(B-1), a layer 916 is sandwiched between one of a pair of surfaces of a secondary battery 913 to form an annular 8B-2, a secondary battery 91 An antenna 918 is provided on the other of the pair of surfaces of the substrate 3 with a layer 917 interposed therebetween. The antenna 918 is For example, the antenna 918 has a function of performing data communication with an external device. For example, an antenna having a shape applicable to antenna 914 and antenna 915 may be applied. As a method for communication between the power storage device and other devices via the antenna 918, NFC is used. It is possible to apply a response method that can be used between the power storage device and other devices, such as the above. Cut.
[0196] 9A, the secondary battery 913 shown in FIG. 7A and FIG. 7B may be A display device 920 may be provided. The display device 920 is electrically connected to the terminal 911 via the terminal 919. It is not necessary to provide the label 910 in the portion where the display device 920 is provided. Note that the same parts as those in the power storage device shown in FIG. The description of the power storage device in FIG. 7B can be used as appropriate.
[0197] The display device 920 displays, for example, an image indicating whether charging is in progress, an image indicating the amount of stored power, etc. The display device 920 may be, for example, an electronic paper, a liquid crystal display device, an electrophotographic display device, or the like. For example, an electroluminescence (EL) display device can be used. By using the par, the power consumption of the display device 920 can be reduced.
[0198] Alternatively, as shown in FIG. 9B, the sensor may be connected to the secondary battery 913 shown in FIG. 7A and FIG. 7B. The sensor 921 may be electrically connected to the terminal 911 via a terminal 922. Note that the same parts as those in the power storage device shown in FIG. The description of the power storage device in FIGS. 7A and 7B can be used as appropriate.
[0199] The sensor 921 may be, for example, a sensor for detecting displacement, position, speed, acceleration, angular velocity, number of rotations, distance, light, etc. , liquid, magnetic, temperature, chemical, sound, time, hardness, electric field, current, voltage, power, radiation, flow It is sufficient if the device has the function of measuring the amount, humidity, gradient, vibration, odor, or infrared rays. By providing the sensor 921, for example, data indicating the environment in which the power storage device is placed can be obtained. It is also possible to detect a signal (such as temperature) and store it in memory within the circuit 912.
[0200] Further, a structural example of the secondary battery 913 will be described with reference to FIGS.
[0201] A secondary battery 913 shown in FIG. 10A has a terminal 951 and a terminal 952 provided inside a housing 930. The winding body 950 is impregnated with an electrolyte inside the housing 930. The terminal 952 is in contact with the housing 930, and the terminal 951 is in contact with the housing by using an insulating material or the like. In FIG. 10A, for convenience, the housing 930 is not in contact with the 9, in reality, the winding body 950 is covered by the housing 930, and the terminals 951 and 95 2 extends outside the housing 930. The housing 930 is made of a metal material (e.g., aluminum). Materials such as rubber or resin materials can be used.
[0202] As shown in FIG. 10B, the housing 930 shown in FIG. 10A is made of a plurality of materials. For example, the secondary battery 913 shown in FIG. The wound body 930b is attached to the housing 930a. 50 are provided.
[0203] The housing 930a can be made of an insulating material such as an organic resin. By using a material such as organic resin on the surface on which the secondary battery 913 is formed, If the shielding of the electric field by the housing 930a is small, the shielding of the housing 930a can be suppressed. Antennas such as antenna 914 and antenna 915 may be provided inside the housing 930b. For example, a metal material can be used.
[0204] The structure of the wound body 950 is shown in FIG. The winding body 950 has a pole 932 and a separator 933. The negative electrode 931 and the positive electrode 932 are stacked on top of each other, and the laminated sheet is wound to form a wound body. The negative electrode 931, the positive electrode 932, and the separator 933 are laminated together. You can stack several of them.
[0205] The negative electrode 931 is connected to the terminal 911 shown in FIG. 7 via one of the terminals 951 and 952. The positive electrode 932 is connected to the terminal 911 shown in FIG. Connected.
[0206] By using the positive electrode active material particles 100 described in the previous embodiment for the positive electrode 932, deterioration is prevented. Therefore, the secondary battery 913 can be made small and highly safe.
[0207] [Laminated secondary battery] Next, an example of a laminated secondary battery will be described with reference to FIGS. If the laminated secondary battery is made flexible, the flexible portion is at least If the secondary battery is mounted on an electronic device that also has a battery, the secondary battery can be bent according to the deformation of the electronic device. can.
[0208] A laminated secondary battery 980 will be described with reference to FIG. The battery 980 has a wound body 993 shown in FIG. 11, a positive electrode 995, and a separator 996. Similar to the wound body 950, a negative electrode 994 and a positive electrode 995 are stacked with a separator 996 interposed therebetween. The laminated sheet is then wound.
[0209] The number of layers of the negative electrode 994, the positive electrode 995, and the separator 996 is determined as required. The negative electrode 994 is connected to the lead electrode 997 and the lead The positive electrode 995 is connected to a negative electrode collector (not shown) via one of the lead electrodes 998. The other of the electrode 997 and the lead electrode 998 is connected to a positive electrode current collector (not shown).
[0210] As shown in FIG. 12B, a film 981 that serves as an exterior body and a film 98 having a recess are 2 are bonded together by thermocompression or the like to form a space in which the above-mentioned wound body 993 is housed. In this way, a secondary battery 980 can be manufactured as shown in FIG. 3 has a lead electrode 997 and a lead electrode 998, a film 981, and a recess The inside of the space surrounded by the film 982 is impregnated with an electrolyte.
[0211] The film 981 and the film 982 having the recesses are made of a metal material such as aluminum. The film 981 and the film 982 having the recesses can be made of a resin material. If a resin material is used as the material, when an external force is applied, the film 981 and the recessed portion The film 982 having the electrode can be deformed to produce a secondary battery having flexibility. can be done.
[0212] In addition, although two films are used in FIG. 12(B) and FIG. 12(C), one film may be used. A space is formed by folding one film, and the above-mentioned wound body 993 is inserted into the space. may be stored.
[0213] By using the positive electrode active material particles 100 described in the previous embodiment for the positive electrode 995, deterioration is prevented. This makes it possible to provide a secondary battery 980 that is small in amount and highly safe.
[0214] In addition, in FIG. 12, a secondary battery 9 having a wound body in a space formed by a film that serves as an exterior body is shown. We have explained the example of 80, but for example, as shown in Figure 13, The space defined by the positive electrode layer may be a space defined by a separator and a negative electrode. stomach.
[0215] The laminated secondary battery 500 shown in FIG. 13(A) includes a positive electrode current collector 501 and a positive electrode active material. A positive electrode 503 having a positive electrode active material layer 502, a negative electrode current collector 504 and a negative electrode active material layer 505. The battery includes a negative electrode 506, a separator 507, an electrolyte 508, and an exterior body 509. A separator 507 is provided between a positive electrode 503 and a negative electrode 506 provided in a body 509. The exterior body 509 is filled with an electrolyte 508. The electrolyte solution shown in the second embodiment can be used.
[0216] In the laminated secondary battery 500 shown in FIG. 13(A), a positive electrode current collector 501 and a negative electrode current collector The positive electrode current collector 504 also serves as a terminal for obtaining electrical contact with the outside. A part of the current collector 501 and the negative electrode current collector 504 is exposed to the outside from the exterior body 509. In addition, the positive electrode current collector 501 and the negative electrode current collector 504 may be arranged in a manner similar to that described above. Instead of exposing it to the outside, a lead electrode is used to connect the lead electrode to the positive electrode current collector 501 or the negative electrode The lead electrode may be exposed to the outside by ultrasonic bonding to the current collector 504 .
[0217] In the laminated secondary battery 500, the exterior body 509 is made of, for example, polyethylene, poly A film made of propylene, polycarbonate, ionomer, polyamide, etc. is coated with a A thin metal film with excellent flexibility, such as aluminum, stainless steel, copper, or nickel, is applied. On the metallic thin film, an insulating synthetic resin such as polyamide resin or polyester resin is applied as the outer surface of the exterior body. A laminate film having a three-layer structure with an oil film can be used.
[0218] An example of the cross-sectional structure of a laminated secondary battery 500 is shown in FIG. For simplicity, A) shows an example consisting of two current collectors, but in reality, it is composed of multiple electrode layers. It consists of:
[0219] In FIG. 13B, as an example, the number of electrode layers is 16. In FIG. 13B, the negative electrode current collector 504 has eight layers. The positive electrode current collector 501 has a structure of 8 layers, totaling 16 layers. The cross section of the extraction part is shown, and eight layers of negative electrode current collector 504 are ultrasonically bonded. The number of electrode layers is not limited to 16, and may be more or less. In addition, when the number of electrode layers is small, the secondary battery can have a larger capacity. In this case, a secondary battery can be made thin and has excellent flexibility.
[0220] An example of the external appearance of a laminated secondary battery 500 is shown in FIGS. 14 and 15. 4 and 15 show a positive electrode 503, a negative electrode 506, a separator 507, an outer casing 509, a positive electrode lead The positive electrode 510 and the negative electrode 511 are connected to each other.
[0221] FIG. 16A shows an external view of a positive electrode 503 and a negative electrode 506. The positive electrode 503 is connected to a positive electrode current collector 50 1, and the positive electrode active material layer 502 is formed on the surface of the positive electrode current collector 501. 503 has a region where the positive electrode current collector 501 is partially exposed (hereinafter referred to as a tab region). 506 has a negative electrode current collector 504, and a negative electrode active material layer 505 is formed on the surface of the negative electrode current collector 504. In addition, the negative electrode 506 has a region where the negative electrode current collector 504 is partially exposed, that is, a tab region. The area and shape of the tab regions of the positive electrode and the negative electrode are not limited to the example shown in FIG. I can't.
[0222] [Method of manufacturing laminated secondary battery] Here, an example of a method for producing a laminated secondary battery shown in FIG. 14 will be described with reference to FIG. This will be explained with reference to FIG.
[0223] First, the negative electrode 506, the separator 507, and the positive electrode 503 are laminated. The negative electrode 506, the separator 507, and the positive electrode 503 are shown. Next, the bonding of the tab regions of the positive electrode 503 and the bonding of the tabs of the positive electrode on the outermost surface are shown. The positive electrode lead electrode 510 is bonded to the region. For example, ultrasonic welding or the like may be used for bonding. Similarly, the bonding between the tab regions of the negative electrodes 506 and the bonding of the negative electrode leads to the tab region of the outermost negative electrode are preferably performed. Then, the metal layer 511 is bonded.
[0224] Next, the negative electrode 506 , the separator 507 and the positive electrode 503 are placed on the exterior body 509 .
[0225] Next, as shown in FIG. 16(C), the exterior body 509 is folded at the portion indicated by the dashed line. After that, the outer periphery of the exterior body 509 is bonded. For example, thermocompression bonding may be used for bonding. 509, so that the electrolyte 508 can be poured in later. An area that is not joined (hereinafter referred to as an inlet) is provided.
[0226] Next, the electrolyte 508 is introduced into the inside of the exterior body 509 through an inlet provided in the exterior body 509. The electrolyte 508 is preferably introduced under a reduced pressure or an inert gas atmosphere. Finally, the inlet is joined. In this way, a laminated secondary battery is produced. A secondary battery 500 can be fabricated.
[0227] By using the positive electrode active material particles 100 described in the previous embodiment for the positive electrode 503, deterioration is prevented. Therefore, the secondary battery 500 can be made small and highly safe.
[0228] [Bendable secondary battery] Next, an example of a bendable secondary battery will be described with reference to FIGS.
[0229] FIG. 17(A) shows a schematic top view of a bendable battery 250. 17(B2) and 17(C) show the cut lines C1-C2 and C3 in FIG. 17(A), respectively. 1 is a schematic cross-sectional view taken along line C3-C4 and line A1-A2. 51, and a positive electrode 211a and a negative electrode 211b housed inside the exterior body 251. A lead 212a electrically connected to the negative electrode 211a, and a lead 212b electrically connected to the negative electrode 211b. The lead 212b extends outside the exterior body 251. In addition to the positive electrode 211a and the negative electrode 211b, an electrolyte (not shown) is enclosed in the region. is.
[0230] The positive electrode 211a and the negative electrode 211b of the battery 250 will be described with reference to FIG. FIG. 18(A) illustrates the stacking order of the positive electrode 211a, the negative electrode 211b, and the separator 214. FIG. 18(B) shows a perspective view of the positive electrode 211a and the negative electrode 211b, as well as a lead 2 12a and a lead 212b.
[0231] As shown in FIG. 18A, the battery 250 includes a plurality of rectangular positive electrodes 211a, a plurality of rectangular The positive electrode 211a and the negative electrode 211b are connected to the positive electrode 211a and the negative electrode 211b. Each of the positive electrodes 211a and 211b has a protruding tab portion and a portion other than the tab. A positive electrode active material layer is formed on the portion other than the tab, and the negative electrode 211b is formed on the portion other than the tab on one surface of the negative electrode 211b. A negative electrode active material layer is formed.
[0232] The surfaces of the positive electrode 211a on which the positive electrode active material layer is not formed and the surfaces of the negative electrode 211b on which the negative electrode active material layer is not formed are The positive electrode 211a and the negative electrode 211b are laminated so that the surfaces on which the porous layer is not formed are in contact with each other. will be done.
[0233] In addition, the surface on which the positive electrode active material layer of the positive electrode 211a is formed and the surface on which the negative electrode active material layer of the negative electrode 211b is formed are A separator 214 is provided between the formed surfaces. Data 214 is shown by a dotted line.
[0234] As shown in FIG. 18B, the positive electrodes 211a and the leads 212a are connected to each other through a joint 215. The negative electrodes 211b and the leads 212b are electrically connected to each other at the joints 211a. Electrical connection is made at 15b.
[0235] Next, regarding the exterior body 251, FIG. 17(B1), FIG. 17(B2), FIG. 17(C), and FIG. This will be explained using (D).
[0236] The exterior body 251 has a film-like shape and is arranged to sandwich the positive electrode 211a and the negative electrode 211b. The exterior body 251 is folded in two at the folded portion 261 and a pair of seal portions 2 The pair of sealing parts 262 are connected to the positive electrode 211a and the negative electrode 211b. The seal portion 26 is provided on either side of the electrode 211b and can also be called a side seal. 3 has a portion overlapping with the lead 212a and the lead 212b, and is also called a top seal. This can be done.
[0237] The exterior body 251 has a ridge line 271 and a valley line 272 at the portion overlapping the positive electrode 211a and the negative electrode 211b. It is preferable that the sealing portion 26 of the exterior body 251 has a corrugated shape in which the grooves 72 are arranged alternately. 2 and the seal portion 263 are preferably flat.
[0238] FIG. 17(B1) is a cross section cut at the portion overlapping with the ridge line 271, and FIG. 17(B2) is a cross section cut at the portion overlapping with the ridge line 271. The cross section is taken at the portion overlapping with the valley line 272. 1 corresponds to a cross section in the width direction of the battery 250, the positive electrode 211a, and the negative electrode 211b.
[0239] Here, the end of the negative electrode 211b in the width direction, i.e., the end of the negative electrode 211b and the seal portion 262 The distance between the battery 250 and the battery 250 is defined as La. In this way, the positive electrode 211a and the negative electrode 211b are deformed so as to be shifted from each other in the length direction. At that time, if the distance La is too short, the exterior body 251 and the positive electrode 211a and the negative electrode 211b are strongly rubbed against each other. In particular, if the metal film of the exterior body 251 is exposed, In this case, the metal film may be corroded by the electrolyte. It is preferable to set the distance La as long as possible. On the other hand, if the distance La is set too large, , the volume of the battery 250 increases.
[0240] In addition, the greater the total thickness of the laminated positive electrode 211a and negative electrode 211b, the greater the It is preferable to increase the distance La between b and the seal portion 262 .
[0241] More specifically, the total thickness of the laminated positive electrode 211a and negative electrode 211b is defined as thickness t. When the thickness t is 0.8 times or more and 3.0 times or less, the distance La is preferably 0.9 times or more and 2. It is preferable that the distance La is 5 times or less, and more preferably 1.0 times or more and 2.0 times or less. By setting the thickness within this range, a battery that is compact and has high reliability against bending can be realized. .
[0242] In addition, when the distance between the pair of seal portions 262 is a distance Lb, the distance Lb is and is sufficiently larger than the width of the negative electrode 211b (here, the width Wb of the negative electrode 211b). This is preferable because it prevents the positive electrode Even if the positive electrode 211a and the negative electrode 211b come into contact with the exterior body 251, Since a part of 11b can be shifted in the width direction, the positive electrode 211a and the negative electrode 211b are This effectively prevents the attachment body 251 from rubbing against each other.
[0243] For example, the difference between the distance Lb between the pair of seal portions 262 and the width Wb of the negative electrode 211b is 1.6 times or more and 6.0 times or less, preferably 1.8 times, the thickness t of the negative electrode 211a and the negative electrode 211b The ratio is preferably from 2.0 to 4.0 times, and more preferably from 2.0 to 4.0 times.
[0244] In other words, it is preferable that the distance Lb, the width Wb, and the thickness t satisfy the relationship of the following formula 2. It is.
[0245]
number
[0246] Here, a is 0.8 or more and 3.0 or less, preferably 0.9 or more and 2.5 or less, and more preferably is greater than or equal to 1.0 and less than or equal to 2.0.
[0247] FIG. 17(C) is a cross section including the lead 212a, and shows the battery 250, the positive electrode 211a and As shown in FIG. 17(C), the bent portion 2 corresponds to a cross section of the negative electrode 211b in the longitudinal direction. In 61, the ends of the positive electrode 211a and the negative electrode 211b in the longitudinal direction and the exterior body 251 are It is preferable to have a space 273 therebetween.
[0248] FIG. 17(D) shows a schematic cross-sectional view of the battery 250 when bent. This corresponds to the cross section taken along line B1-B2 in FIG.
[0249] When the battery 250 is bent, the part of the exterior body 251 located on the outside of the bend stretches, and the part located on the inside More specifically, the part located on the outside of the exterior body 251 is deformed so as to shrink. The outer casing 251 deforms so that the amplitude of the wave becomes smaller and the period of the wave becomes larger. The part located inside the ridge deforms so that the wave amplitude is large and the wave period is small. In this way, the deformation of the exterior body 251 reduces the load applied to the exterior body 251 due to bending. Since the stress is relieved, the material that constitutes the exterior body 251 does not need to expand or contract. As a result, the battery 250 can be bent with a small force without damaging the exterior body 251.
[0250] Furthermore, as shown in FIG. 17(D), when the battery 250 is bent, the positive electrode 211a and the negative electrode 21 At this time, the stacked positive electrodes 211a and negative electrodes 211b are shifted relative to each other. Since one end of 211b on the side of the seal portion 263 is fixed by the fixing member 217, The amount of deviation increases toward the positive electrode 21. The stress applied to the positive electrode 211a and the negative electrode 211b is relieved, and the positive electrode 211a and the negative electrode 211b themselves As a result, the positive electrode 211a and the negative electrode 211b do not need to expand and contract. The battery 250 can be bent.
[0251] In addition, a space 273 is provided between the positive electrode 211a and the negative electrode 211b and the exterior body 251. As a result, when the battery is bent, the positive electrode 211a and the negative electrode 211b located on the inside are bent into the exterior body 25. It can move relative to 1 without touching it.
[0252] The battery 250 illustrated in FIGS. 17 and 18 does not break the exterior body even when repeatedly bent and stretched. The battery characteristics are also less likely to deteriorate. The battery 250 has a positive electrode 211a containing the positive electrode active material described in the previous embodiment. By using the particles 100, it is possible to obtain a secondary battery with less deterioration and higher safety. Cut.
[0253] (Embodiment 4) In this embodiment, an example in which a secondary battery according to one embodiment of the present invention is mounted on an electronic device will be described. do.
[0254] First, as described in part of the third embodiment, a bendable secondary battery is mounted on an electronic device. An example is shown in Figure 19. As an electronic device that uses a bendable secondary battery, Revision equipment (also called television or television receiver), computer models, etc. Digital cameras, digital video cameras, digital photo frames, mobile phones ( Mobile phones, also called mobile phone devices, portable game machines, portable information terminals, audio playback devices, Examples include large game machines such as dick machines.
[0255] In addition, the flexible secondary battery can be mounted on the inner or outer walls of houses or buildings, or on the inside or outside of automobiles. It is also possible to incorporate it along the curved surfaces of the interior or exterior of the vehicle.
[0256] FIG. 19A shows an example of a mobile phone. A mobile phone 7400 includes a housing 7401. In addition to the display unit 7402, operation buttons 7403, an external connection port 7404, The mobile phone 7400 is equipped with a speaker 7405, a microphone 7406, etc. It has a battery 7407.
[0257] FIG. 19B shows the mobile phone 7400 in a curved state. When the battery is deformed by applying an external force to the battery, the secondary battery installed inside the battery is released. The secondary battery 7407 is also bent. At this time, the state of the bent secondary battery 7407 is shown in FIG. The secondary battery 7407 is a thin secondary battery. The secondary battery 7407 is bent. The secondary battery 7407 is fixed in a state in which the lead electrode is electrically connected to the current collector. It has.
[0258] FIG. 19D shows an example of a bangle-type display device. The portable display device 7100 is The device includes a housing 7101 , a display unit 7102 , operation buttons 7103 , and a secondary battery 7104 . FIG. 19E shows the bent state of the secondary battery 7104. When the device is attached to the user's arm, the housing may deform and cause damage to part of the secondary battery 7104 or The total curvature changes. Note that the degree of curvature at any point on the curve is expressed as the radius of the corresponding circle. The value expressed is called the radius of curvature, and the inverse of the radius of curvature is called the curvature. Within the range of 40 mm to 150 mm, a part of the main surface of the case or the secondary battery 7104 The radius of curvature of the main surface of the secondary battery 7104 is 40 mm or more and 150 mm or less. If the distance is within the range of mm or less, high reliability can be maintained.
[0259] FIG. 19(F) shows an example of a wristwatch-type portable information terminal. The portable information terminal 7200 is , a housing 7201, a display unit 7202, a band 7203, a buckle 7204, and an operation button 72 05, input / output terminal 7206, etc.
[0260] The portable information terminal 7200 is capable of carrying out mobile telephone calls, e-mails, viewing and creating documents, playing music, and using the Internet. - It can run various applications such as internet communication and computer games. do.
[0261] The display unit 7202 has a curved display surface, and displays images along the curved display surface. The display portion 7202 is provided with a touch sensor, and can be used to input a touch signal to the screen using a finger or a stylus. For example, the icon 72 displayed on the display unit 7202 can be operated by touching it. You can launch the application by touching 07.
[0262] The operation button 7205 is used to set the time, turn the power on and off, and turn wireless communication on and off. It has various functions such as operation, silent mode activation and deactivation, power saving mode activation and deactivation, etc. For example, an operating system installed in the portable information terminal 7200 can The function of the operation button 7205 can also be freely set using the stem.
[0263] In addition, the mobile information terminal 7200 is capable of performing short-distance wireless communication according to a communication standard. For example, by communicating with a wireless headset, You can also make calls.
[0264] The portable information terminal 7200 also includes an input / output terminal 7206, and a connector for connecting to other information terminals. Data can be exchanged directly through the input / output terminal 7206. The charging operation can be performed by wireless power supply without going through the input / output terminal 7206. This is also possible.
[0265] A display portion 7202 of a portable information terminal 7200 includes a secondary battery of one embodiment of the present invention. For example, the secondary battery 7104 shown in FIG. 19E is curved inside the housing 7201. or may be incorporated in a bendable state inside the band 7203.
[0266] The portable information terminal 7200 preferably has a sensor. For example, a fingerprint sensor may be used as the sensor. Sensors for human body such as pulse sensors, body temperature sensors, touch sensors, pressure sensors, acceleration sensors It is preferable that the above-mentioned components are mounted on the vehicle.
[0267] FIG. 19G shows an example of a wristband-type display device. The display device 7300 includes a display unit 7 The display device 7300 includes a display 304 and a secondary battery of one embodiment of the present invention. The display unit 7304 may be equipped with a touch sensor, and may function as a portable information terminal. It is also possible.
[0268] The display surface of the display unit 7304 is curved, and the display can be performed along the curved display surface. In addition, the display device 7300 can display a display state by short-distance wireless communication according to a communication standard. The situation can be changed.
[0269] The display device 7300 also has an input / output terminal, and can directly connect to other information terminals via a connector. It is also possible to charge the device via the input / output terminals. The charging operation may be performed by wireless power supply without going through the input / output terminals.
[0270] Next, FIG. 20(A) and FIG. 20(B) show an example of a foldable tablet terminal. The tablet terminal 9600 shown in FIGS. 20(A) and 20(B) includes a housing 9630a, A housing 9630b, a movable part 9640 connecting the housings 9630a and 9630b, and a display unit 9 631, display mode changeover switch 9626, power switch 9627, power saving mode switch The display unit 9625 has a switch 9625, a fastener 9629, and an operation switch 9628. The 631 uses a flexible panel, allowing it to be a tablet with a larger display area. FIG. 20A shows a tablet terminal 9600 in an open state. FIG. 20B shows the tablet terminal 9600 in a closed state.
[0271] The tablet terminal 9600 also includes a battery storage device inside the housing 9630a and the housing 9630b. The power storage unit 9635 is connected to the housing 9630a through the movable portion 9640. It is located across 9630b.
[0272] A part of the display unit 9631 can be used as a touch panel area, and the user can operate the displayed operation keys. You can enter data by touching the screen. You can also switch the keyboard display on the touch panel. By touching the area where the replacement button is displayed with your finger or a stylus, the display 9631 Keyboard buttons can be displayed.
[0273] A display mode changeover switch 9626 is used to change the display orientation between portrait and landscape. You can switch between black and white and color display. The touch 9625 detects when in use by an optical sensor built into the tablet terminal 9600. The brightness of the display can be optimized according to the amount of external light. In addition to optical sensors, other sensors such as gyros and acceleration sensors that detect tilt are also available. The device may be built-in.
[0274] FIG. 20B shows the tablet terminal in a closed state. The tablet terminal includes a housing 9630 and a solar cell 96 33, a charge / discharge control circuit 9634 including a DCDC converter 9636. A secondary battery according to one embodiment of the present invention is used as 9635.
[0275] In addition, since the tablet terminal 9600 can be folded in two, when not in use, The housing 9630b can be folded so that the housing 9630a and the housing 9630b overlap each other. Since the display portion 9631 can be protected, the durability of the tablet terminal 9600 can be improved. In addition, the power storage unit 9635 using the secondary battery of one embodiment of the present invention has a high capacity and a good cycle life. Because of its excellent thermal properties, it is possible to provide tablet devices that can be used for long periods of time. do.
[0276] In addition, the tablet terminals shown in Figs. 20(A) and 20(B) can store various information. Functions for displaying information (still images, videos, text images, etc.), calendars, dates, or times, etc. A function to display the information on the display unit, and to operate or edit the information displayed on the display unit by touch input. , touch input function, function to control processing by various software (programs), etc. may have the following structure:
[0277] The solar cell 9633 attached to the surface of the tablet device supplies power to the touch panel, The solar cell 9633 can be provided to a display unit, a video signal processor, or the like. The structure can be provided on one or both sides of the power storage unit 9630, and can efficiently charge the power storage unit 9635. It can be said that it is completed.
[0278] The configuration and operation of the charge / discharge control circuit 9634 shown in FIG. A block diagram is shown in FIG. 20C. 5, DC-DC converter 9636, converter 9637, switches SW1 to SW3, table The display unit 9631 is shown, which includes a storage battery 9635, a DC-DC converter 9636, and a The inverter 9637 and the switches SW1 to SW3 are connected to the charge / discharge control circuit 96 shown in FIG. This corresponds to 34.
[0279] First, an example of operation in which power is generated by the solar cell 9633 using external light will be described. The power generated by the solar cell is converted to a voltage for charging the storage battery 9635 by the DCDC controller. The voltage is increased or decreased by a inverter 9636. When power from the 9633 is used, switch SW1 is turned on and the converter 9637 The voltage is increased or decreased to a voltage required for the display unit 9631. When not displaying the data, turn switch SW1 off and switch SW2 on to store the data. It is sufficient to configure the device to charge the battery 9635.
[0280] The solar cell 9633 is shown as an example of a power generating means, but is not limited thereto. Storage of electricity by other power generation means such as piezoelectric elements and thermoelectric conversion elements For example, the device may be configured to transmit and receive power wirelessly (contactlessly). It is also possible to combine it with a non-contact power transmission module that charges the battery by using a contactless power transmission method, or other charging methods. This is also fine.
[0281] FIG. 21 shows another example of electronic equipment. In FIG. 21, a display device 8000 according to one embodiment of the present invention is 8 is an example of an electronic device using a secondary battery 8004 according to an embodiment. 8000 corresponds to a display device for receiving TV broadcasts, and includes a housing 8001, a display unit 8002, and a speaker unit. The secondary battery 8004 according to one embodiment of the present invention includes a housing 8003 and a secondary battery 8004. The display device 8000 is provided inside a body 8001. The display device 8000 receives power from a commercial power source. Alternatively, the power stored in the secondary battery 8004 can be used. Even when power cannot be supplied from a commercial power source due to a power outage or the like, the present invention according to one embodiment of the present invention By using the secondary battery 8004 as an uninterruptible power supply, the display device 8000 can be used. do.
[0282] The display unit 8002 may be a liquid crystal display device, an emitting device having light emitting elements such as organic EL elements in each pixel, or the like. Device, electrophoretic display device, DMD (Digital Micromirror Devi ce), PDP (Plasma Display Panel), FED (Field A semiconductor display device such as a 3D Emission Display can be used.
[0283] In addition, display devices are used for TV broadcast reception, personal computers, advertising displays, etc. , all display devices for displaying information are included.
[0284] In FIG. 21, a stationary lighting device 8100 includes a secondary battery 81 according to one embodiment of the present invention. 8101, a light source 8102, and a light source 8103 are used. 21, the secondary battery 8103 is disposed in the housing 81. 8102 is installed inside a ceiling 8104. However, the secondary battery 8103 may be provided inside the housing 8101. The device 8100 can receive power from a commercial power source, or store power in a secondary battery 8103. Therefore, when the power supply from the commercial power source is cut off due to a power outage, Even when the electricity cannot be received, the secondary battery 8103 according to one embodiment of the present invention is used as an uninterruptible power source. This enables the lighting device 8100 to be used.
[0285] In addition, FIG. 21 illustrates a lighting device 8100 that is installed on a ceiling 8104. However, in the secondary battery according to one embodiment of the present invention, other than the ceiling 8104, for example, the side wall 8105, the floor 8106, 106, the window 8107, etc., can be used as a fixed lighting device, or a tabletop lighting device. The present invention can also be used in lighting devices of this type.
[0286] In addition, the light source 8102 may be an artificial light source that artificially obtains light using electricity. Specifically, incandescent lamps, fluorescent lamps and other discharge lamps, light emitting diodes (LEDs) and organic electroluminescence (EL) elements The element is an example of the artificial light source.
[0287] In FIG. 21, an air conditioner having an indoor unit 8200 and an outdoor unit 8204 is as follows: 8 is an example of an electronic device using a secondary battery 8203 according to one embodiment of the present invention. The device 8200 includes a housing 8201, an air outlet 8202, a secondary battery 8203, and the like. 8 illustrates an example in which the secondary battery 8203 is provided in the indoor unit 8200. The battery 8203 may be provided in the outdoor unit 8204. A secondary battery 8203 may be provided in both the power source 8202 and the power source 8204. The power supply can be provided from a commercial power source, or the power stored in the secondary battery 8203 can be used. In particular, a secondary battery 82 is provided in both the indoor unit 8200 and the outdoor unit 8204. If 03 is installed, when power cannot be supplied from the commercial power source due to a power outage, etc. In addition, by using the secondary battery 8203 according to one embodiment of the present invention as an uninterruptible power supply, The conditioner can be used.
[0288] In Figure 21, a separate type air conditioner consisting of an indoor unit and an outdoor unit is shown. As an example, an all-in-one air conditioner that has both indoor and outdoor unit functions in a single housing. The secondary battery according to one embodiment of the present invention can also be used for the conditioner.
[0289] In FIG. 21, an electric refrigerator-freezer 8300 includes a secondary battery 8304 according to one embodiment of the present invention. Specifically, an electric refrigerator-freezer 8300 includes a housing 8301, a refrigerator It has a storage compartment door 8302, a freezer compartment door 8303, a secondary battery 8304, etc. A secondary battery 8304 is provided inside the housing 8301. The electric refrigerator-freezer 8300 is It can receive power from a commercial power source, or use the power stored in the secondary battery 8304. Therefore, when power cannot be supplied from commercial power sources due to a power outage, etc. However, by using the secondary battery 8304 according to one embodiment of the present invention as an uninterruptible power supply, It will be possible to use the 8300 freezer refrigerator.
[0290] In addition, during periods when electronic devices are not in use, especially during periods when the total amount of power that can be supplied by commercial power suppliers is low, During times when the ratio of electricity actually used (called the electricity usage rate) is low, By storing power in the battery, it is possible to prevent high power usage outside of the above time periods. For example, in the case of the electric refrigerator-freezer 8300, when the temperature is low, the refrigerator compartment door 830 2. During the night when the freezer door 8303 is not opened or closed, the secondary battery 8304 stores electricity. Then, as the temperature rises, the refrigerator door 8302 and the freezer door 8303 are opened and closed. During the daytime, when the vehicle is turned on, the secondary battery 8304 is used as an auxiliary power source, and the daytime power usage rate is can be kept low.
[0291] In addition to the electronic devices described above, the secondary battery according to one embodiment of the present invention can be mounted on various electronic devices. According to one embodiment of the present invention, a secondary battery which is less deteriorated and highly safe can be provided. Therefore, when the secondary battery according to one embodiment of the present invention is installed in the electronic device described in this embodiment, By doing so, it is possible to provide an electronic device with a longer life and higher safety. The embodiment can be implemented in appropriate combination with other embodiments.
[0292] (Embodiment 5) In this embodiment, an example in which a secondary battery according to one embodiment of the present invention is mounted on a vehicle will be described.
[0293] When a secondary battery is installed in a vehicle, it becomes a hybrid vehicle (HEV), electric vehicle (EV), or powertrain. This will make it possible to realize next-generation clean energy vehicles such as plug-in hybrid vehicles (PHEVs). .
[0294] FIG. 22 illustrates an example of a vehicle using a secondary battery according to one embodiment of the present invention. The automobile 8400 shown in FIG. 1 is an electric automobile that uses an electric motor as a power source for driving. Alternatively, an electric motor and an engine can be selected as the power source for driving. The hybrid vehicle can be realized by using the secondary battery according to one embodiment of the present invention. In this way, a vehicle with a long driving range can be realized. The secondary battery not only drives the electric motor 8406, but also the headlights 8401 and the lamp Power can be provided to a light emitting device such as a room light (not shown).
[0295] In addition, the secondary battery is used for the display of the speedometer, tachometer, etc. of the automobile 8400. The secondary battery can supply power to the navigation device of the automobile 8400. The present invention can provide power to semiconductor devices such as power distribution systems.
[0296] The automobile 8500 shown in FIG. 22(B) has a plug-in secondary battery 8024. The device can be charged by receiving power from an external charging facility using a plug-in method or a non-contact power supply method. FIG. 22(B) shows a charging device 8021 mounted on a ground and a charging device 8022 mounted on a vehicle 8500. The secondary battery 8024 is being charged via a cable 8022. When charging, the charging method and connectors must comply with standards such as CHAdeMO (registered trademark) and Combo. The charging device 8021 is a charging station installed in a commercial facility. For example, plug-in technology can be used to The secondary battery 8024 installed in the automobile 8500 can be charged by the power supply. Charging is performed by converting AC power to DC power via a conversion device such as an ACDC converter. It is possible.
[0297] Although not shown, a power receiving device is mounted on the vehicle and receives power from a ground power transmitting device in a non-contact manner. In this non-contact power supply method, a power transmission device is installed on the road or exterior wall. By incorporating this technology, charging can be done not only when the vehicle is stopped but also while it is moving. Using this method, electric power may be transmitted between vehicles. A solar battery may be installed to charge the secondary battery when the vehicle is stopped or running. The power can be supplied using an electromagnetic induction method or a magnetic resonance method.
[0298] FIG 22C shows an example of a two-wheeled vehicle using the secondary battery of one embodiment of the present invention. The scooter 8600 shown in (C) has a secondary battery 8602, side mirrors 8601, and a turn signal. The secondary battery 8602 can supply electricity to the direction indicator light 8603. can.
[0299] In addition, the scooter 8600 shown in FIG. 22(C) has a secondary battery 860 in the storage space under the seat 8604. 2 can be stored. The secondary battery 8602 can be stored in the under-seat storage 8604 even if it is small. , and can be stored in the under-seat storage space 8604.
[0300] According to one embodiment of the present invention, a secondary battery that is less prone to deterioration and has high safety can be obtained. Therefore, by installing it in a vehicle, it is possible to prevent a decrease in cruising range and acceleration performance. In addition, the vehicle can be made highly safe. In this case, for example, the power generated by commercial power plants during peak periods of electricity demand can be used as a power supply source for commercial power plants. It is possible to avoid using commercial power sources during peak power demand periods. If this can be avoided, it will contribute to energy conservation and reduction of carbon dioxide emissions. In addition, cobalt-free batteries have little deterioration and can be used for a long period of time as highly safe secondary batteries. This will reduce the use of rare metals, including
[0301] This embodiment mode can be implemented in appropriate combination with other embodiment modes. EXAMPLES
[0302] In this embodiment, a positive electrode active material having magnesium, fluorine, and oxygen at and near the grain boundaries is used. The crystal grains and crystallites in the active material were identified by TEM observation and STEM-EDX analysis. The concentration distribution of the grain boundaries was confirmed. The sample was one of sample A, which is one embodiment of the present invention. As material A, nickel-containing magnesium, fluorine and oxygen at and near the grain boundaries is used. We prepared lithium manganese-cobalt oxide. We also prepared lithium nickel-manganese-cobalt oxide. The composition is LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2 is assumed. LiNi 1 / 3 Mn 1 / 3Co 1 / 3 O2 has a layered rock-salt type crystal structure.
[0303] <Preparation of Sample A> The preparation of sample A will be described.
[0304] As shown in step S11 of the flow in FIG. 3, starting materials were prepared. Charcoal was used as a lithium source. Lithium oxide (Li2CO3), nickel oxide (NiO) as a nickel source, and manganese source As a source of cobalt, tricobalt tetroxide (Co3O4) is used. Magnesium oxide (MgO) as the magnesium source, lithium fluoride (LiF) as the fluorine source Specifically, 3.1398 g (42.49 mmol) of Li2CO3 was weighed out. , 2.1159 g (28.33 mmol) of NiO, and 2.4627 g (28. 33 mmol), 2.2033 g (9.15 mmol) of Co3O4, 0.03 43 g (0.85 mmol) of ZnO and 0.0441 g (1.70 mmol) of LiF were weighed out. This is the ratio of magnesium atoms to the total number of nickel, manganese, and cobalt atoms. The ratio m of the number of magnesium atoms is 0.010 (1.0%). The amount is such that the ratio of the number of fluorine atoms, n, is 2.0. The NiO was manufactured by Kojundo Chemical Laboratory Co., Ltd. (catalog number: LIH06XB). Catalog number: NIO04PB) was used. MnO2 was manufactured by Kojundo Chemical Laboratory Co., Ltd. (catalog number: NIO04PB). Co3O4 was manufactured by Kojundo Chemical Laboratory Co., Ltd. (catalog number: COO09PB). MgO was manufactured by Kojundo Chemical Laboratory Co., Ltd. (catalog number: MGO12 LiF was manufactured by Kojundo Chemical Laboratory (catalog number: LIH10XB). there was.
[0305] Next, as shown in step S12, the starting materials weighed in step S11 were mixed. A wet ball mill was used for mixing. Specifically, the balls were 3 mm in diameter and acetone was used as the solvent. The mixture was ground and mixed for 2 hours at a rotation speed of 300 rpm.
[0306] Next, as shown in step S13, the material mixed in step S12 is subjected to a first heating. The first heating was performed using a muffle furnace at a heating rate of 200°C / hr from room temperature for 1000 h. The temperature was raised to ℃, and heating was carried out at 1000℃ for 10 hours. The heating was performed in a dry air atmosphere, and the
[0307] By the first heating in step S13, lithium nickel manganese cobalt oxide can be synthesized. At this point, a part of magnesium and fluorine is considered to be in a state of solid solution in the grain boundaries and grains.
[0308] Next, as shown in step S14, the material heated in step S13 was cooled to room temperature, and composite 1 was obtained. After cooling, the obtained composite 1 was crushed to reduce the particle size of composite 1. A 53μm mesh was used for the crushing process.
[0309] Next, as shown in step S15, a second heating was performed on composite 1 obtained in step S14. The second heating was carried out using a muffle furnace, with a heating rate of 200℃ / hr from room temperature to 800℃, and heating was carried out at 800℃ for 2 hours. The heating was performed in a dry air atmosphere, and the flow rate of the dry atmosphere was set to 10L / min.
[0310] By performing the second heating in step S15, it is possible to promote the segregation of magnesium and fluorine contained in the starting materials to the grain boundaries of lithium nickel manganese cobalt oxide.
[0311] Next, as shown in step S16, the composite 1 heated in step S15 was cooled to room temperature and recovered to obtain sample A.
[0312] <TEM Observation, STEM Observation, EDX Measurement> Next, sample A was processed by a focused ion beam (FIB). The cross section of sample A was sliced and observed by TEM and STEM. The composition was analyzed by X-ray diffraction (EDX) measurement. TEM, STEM observation and EDX measurement were performed using JEOL J The EM-ARM200F was used, the acceleration voltage was 200 kV, and the beam diameter was approximately 0.1 nmφ. .
[0313] In the EDX measurement, the elemental analyzer was an energy dispersive X-ray analyzer JED manufactured by JEOL Ltd. A Si drift detector was used for X-ray detection. The detection limit was about 1 atomic %. It is possible to detect elements from uranium (U) with atomic number 92 to uranium (B). do.
[0314] A TEM image (bright field image) of the cross section of sample A is shown in FIG. 23(A). The magnification of FIG. 23(A) is 10 In FIG. 23(A), the area where the density (brightness) of the TEM image is approximately uniform is the crystal orientation. The density (brightness) of the TEM image changes in the area where the crystal is considered to be single crystal. This is thought to be a grain boundary. A schematic diagram corresponding to FIG. 23(A) is shown in FIG. 23(B). FIG. 23(A) As shown in FIG. 23B, the positive electrode active material particles have a plurality of crystal grains 1101 and gaps between the crystal grains. It was confirmed that there was a grain boundary 1103 in the crystalline structure.
[0315] A STEM image (bright field image) of the cross section of sample A is shown in Fig. 24(A), and a HAADF-STE The M image is shown in Figure 24(B). The magnification of Figures 24(A) and 24(B) is 8 million times. In Fig. 24(A) and Fig. 24(B), crystal lattice images were observed in the crystal grain regions.
[0316] Next, we will explain the EDX spectrum of the cross section of sample A. In EDX measurement, electrons are The energy and frequency of the characteristic X-rays generated are measured, and the EDX scan is performed. The HAADF-STEM image and EDX measurement points of the cross section of sample A are shown in Figure 25. The EDX measurement points are five points, point 1 to point 5. Point 4 is the grain boundary and its vicinity, and point 1 and point 5 are the grain boundary and its vicinity. The EDX spectrum and quantitative results for point 1 were taken at a position away from the crystal grain, i.e., inside the grain. Figure 26, point 2 in Figure 27, point 3 in Figure 28, point 4 in Figure 29, poi nt5 is shown in FIG. 30. In FIG. 26 to FIG. 30, the horizontal axis represents the characteristic X-ray energy (Ene The vertical axis indicates the characteristic X-ray intensity [Counts].
[0317] At points 1 to 5, carbon (C), oxygen (O), fluorine (F), magnesium Magnesium (Mg), Silicon (Si), Phosphorus (P), Sulfur (S), Calcium (Ca), Manganese (Mn), cobalt (Co), and nickel (Ni) electron transitions to their respective K shells The spectrum obtained was separated into the individual elements, and the atomic concentrations were calculated. I got a degree.
[0318] Next, we will explain EDX area analysis. The area is scanned and measured, and the area is analyzed in two dimensions. In this embodiment, the EDX measurement is performed on the area It was done using 256 vertical x 256 horizontal points.
[0319] FIG. 31(A) shows an HAADF-STEM image of the area of sample A where EDX area analysis was performed. The EDX area analysis was performed on the region including the grains and grain boundaries. In the EDX area analysis, the carbon mapping image is shown in FIG. 31(B), the oxygen mapping image is shown in FIG. 31(C), Fluorine in Fig. 31(D), magnesium in Fig. 31(E), silicon in Fig. 31(F), phosphorus in Fig. Figure 32(A), sulfur in Figure 32(B), calcium in Figure 32(C), manganese in Figure 32(D ), cobalt is shown in Figure 32(E), and nickel is shown in Figure 32(F).
[0320] 31(B) to 31(F) and 32(A) to 32(F) show characteristics measured by EDX. The map shows the characteristic X-ray intensity, with measurement points with low characteristic X-ray intensity shown in light color (white) and The measurement points with higher X-ray intensity are shown in darker (black) colors. In other words, the measurement points with lighter (white) colors are The dark (black) measurement points indicate a low atomic concentration, while the dark (black) measurement points indicate a high atomic concentration. 1(B) to 31(F) and 32(A) to 32(F) show the distribution within the region in a clear manner. As shown in Fig. 1, the scale of the characteristic X-ray intensity is changed for each element.
[0321] As shown in FIGS. 31(B) to 31(F) and 32(A) to 32(F), the grain boundaries At and near the site, there are high concentrations of fluorine, magnesium, silicon and calcium. It was confirmed that silicon and calcium were contained in the reagents used as raw materials. It is believed that there were.
[0322] EDX area analysis shown in Figs. 31(B) to 31(F) and Figs. 32(A) to 32(F) The data of the linear region is extracted from the data, and the distribution of atomic concentration within the positive electrode active material particles is evaluated. In this way, one-dimensional evaluation of a linear region is sometimes called line analysis.
[0323] FIG. 33(A) shows an HAADF-STEM image of the area of sample A where EDX line analysis was performed. In FIG. 33(A), the area where the EDX line analysis was performed is indicated by an arrow. The analysis was performed on the crystal grains, the grain boundaries, and the regions spanning the crystal grains.
[0324] The carbon atom concentration in the EDX line analysis of the area shown in FIG. 33(A) is shown in FIG. 34(A). Oxygen in Fig. 34(B), fluorine in Fig. 34(C), magnesium in Fig. 34(D), silicon in Fig. Fig. 34(E), Phosphorus Fig. 34(F), Sulfur Fig. 35(A), Calcium Fig. 35(B), Manganese is shown in Figure 35(C), cobalt in Figure 35(D), and nickel in Figure 35(E).
[0325] In Figures 34(A) to 34(F) and Figures 35(A) to 35(E), the horizontal axis represents distance ( The vertical axis indicates the atomic concentration [atomic%]. The distance is measured from the black circle at one end of the arrow shown in FIG. 34(A) as the starting point (distance = 0 nm) to the other end The vertical axis shows the atomic concentration of carbon, oxygen, etc. , fluorine, magnesium, silicon, phosphorus, sulfur, calcium, manganese, cobalt and The number of atoms of each element when the total number of nickel atoms is 100 atomic % The ratio of
[0326] As shown in Figs. 33(A), 34(A) to 34(F), and 35(A) to 35(E), As shown in Fig. 1, compared with the grain region, the grain boundaries and their vicinity are rich in fluorine, magnesium, and silicon. It was also confirmed that the concentrations of calcium and arsenic in the grain boundaries and their vicinity were high. It was found that the vicinity had a region with a width of 1 nm or more and 10 nm or less.
[0327] It was confirmed that the grain boundaries and their vicinity contained oxygen, magnesium, and fluorine. It was found that the grain boundaries and their vicinity contained magnesium oxide. It is believed that some of the oxygen in the silicon is replaced by fluorine.
[0328] On the other hand, in the grain region, fluorine, magnesium, silicon and calcium were at the detection limit. It was Lu.
[0329] Phosphorus and sulfur were at the lower detection limit both in the grains and at the grain boundaries.
[0330] Carbon was detected in the crystal grains and grain boundaries, but the carbon coating film was not used as a protective film. The carbon concentration mentioned above is thought to include carbon originating from the carbon coating film. Therefore, the true carbon concentration of the grains and grain boundaries could not be determined.
[0331] Compared to the grains, the grain boundaries and their vicinity are dominated by the transition metals manganese, cobalt, and nickel. It was confirmed that the atomic concentration of Kel was lower.
[0332] The total atomic concentration of the transition metals nickel, manganese, and cobalt is shown in Figure 35(F). In FIG. 35(F), the horizontal axis indicates distance (nm) and the vertical axis indicates nickel. Total atomic concentration of nickel, manganese and cobalt (Ni+Mn+Co) [atomic%] Specifically, the total atomic concentration of nickel, manganese and cobalt (Ni+Mn+Co ) is the total atomic concentration of nickel, manganese, and cobalt at each EDX measurement point. In sample A, the total atomic concentration of nickel, manganese and cobalt (Ni+M n+Co) can be said to be the atomic concentration of the transition metal. It was found that the concentration of transition metal atoms at and near the grain boundaries tends to be lower than that in the other regions. In addition, in the crystal grain region, there is no large variation in the atomic concentration of the transition metal, and it is approximately It was found to be uniform.
[0333] The ratio of the atomic concentration of magnesium (Mg) to the atomic concentration of transition metals in the crystal grains is shown. In FIG. 36(A), the horizontal axis represents distance [nm]. The vertical axis shows the ratio of the atomic concentration of magnesium to the atomic concentration of transition metals in the grains ( Mg / Tr-Metal) (arb. unit).
[0334] The atomic concentration of transition metals in crystal grains (Tr-Metal) is explained. The atomic concentration of the transition metal in the crystal grains (Tr-Metal) is the atomic concentration of the transition metal in the crystal grains (Tr-Metal). Specifically, the average concentration of magnesium (Mg) was measured at the detection limit. The region was taken as the crystal grain region, and the average atomic concentration of the transition metal in that region was calculated. The crystal grain region used in the calculation is indicated by an arrow in FIG.
[0335] As shown in FIG. 36(A), the grain boundaries and their vicinity are characterized by the atomic concentration of the transition metal in the grains. The ratio of magnesium atomic concentration to the concentration (Mg / Tr-Metal) is 0.030 or more. Magnesium is segregated at and near the grain boundaries. It was found that the grain boundaries and their vicinity are believed to contain magnesium oxide. Sample A, which is one embodiment of the present invention, has magnesium oxide at and near the grain boundaries. The positive electrode active material particles become chemically and structurally stable, and the transition metal dissolves into the electrolyte. It is possible to suppress the deterioration of the positive electrode active material, such as the desorption of the positive electrode group and the instability of the crystal structure. It is possible to prevent the positive electrode active material particles from cracking. It is also possible to prevent oxygen from being released from the positive electrode active material particles. By using such positive electrode active material particles, deterioration of the power storage device can be suppressed. In addition, a highly safe power storage device can be obtained. The amount of lithium contained in the positive electrode decreases, making the crystal structure of the positive electrode active material particles more susceptible to transformation. For this reason, sample A is particularly preferable as the positive electrode active material particles.
[0336] The atomic concentration of fluorine relative to the atomic concentration of transition metals (Tr-Metal) in the crystal grains The ratio is shown in Figure 36(B). In Figure 36(B), the horizontal axis is distance [n m], and the vertical axis represents the ratio of the atomic concentration of fluorine to the atomic concentration of transition metals in the crystal grains ( F / Tr-Metal).
[0337] As shown in FIG. 36(B), the grain boundaries and their vicinity are characterized by the atomic concentration of the transition metal in the grains. The ratio of fluorine atom concentration to fluorine concentration (F / Tr-Metal) is 0.030 or more. It was found that the presence of fluorine at and near the grain boundaries reduces the It was found that magnesium could be efficiently segregated in the vicinity of the layer.
[0338] In this specification, the term "atomic concentration ratio" and the term "atomic number ratio" are synonymous. The ratio of the number of atoms in the Mg / Tr-Metal alloy can be replaced with the ratio of the number of atoms in the Mg / Tr-Metal alloy. is the ratio of the atomic concentration of magnesium to the atomic concentration of the transition metal in the grain. It is also known as the ratio of the number of magnesium atoms to the number of transition metal atoms in a grain. I can say.
[0339] The total atomic concentration of nickel, manganese and cobalt (Ni+Mn+ The ratio of the atomic concentration of magnesium (Mg) to that of Co is shown in FIG. In C), the horizontal axis indicates distance [nm], and the vertical axis indicates EDX measurement points. The ratio of magnesium atoms to the total atomic concentration of nickel, manganese, and cobalt per The concentration ratio (Mg / (Ni+Mn+Co)) is shown.
[0340] The total atomic concentration of nickel, manganese and cobalt (Ni+Mn+ Co) is the same as the data shown in FIG. 35(F).
[0341] As shown in FIG. 36(C), the grain boundaries and their vicinity are composed of nickel and manganese in the grains. The ratio of the atomic concentration of magnesium to the total atomic concentration of nickel and cobalt (Mg / (Ni+ It was found that there is an area where the Mn+Co) is 0.030 or more. It was found that magnesium was segregated in the vicinity.
[0342] The total atomic concentration of nickel, manganese and cobalt (Ni+Mn+ The ratio of the atomic concentration of fluorine to that of Co is shown in FIG. The horizontal axis shows the distance [nm], and the vertical axis shows the nickel The ratio of the atomic concentration of fluorine to the total atomic concentration of manganese and cobalt (F / (Ni +Mn+Co).
[0343] As shown in FIG. 36(D), the grain boundaries and their vicinity are characterized by the atomic concentration of the transition metal in the grains. The ratio of fluorine atom concentration to the concentration (F / (Ni+Mn+Co)) is 0.030 or more. It was found that the grain boundary and its vicinity have fluorine, which It was found that magnesium can be efficiently segregated in and around the area.
[0344] Similarly, EDX measurement was performed on another portion of sample A.
[0345] FIG. 37(A) shows an HAADF-STEM image of the area of sample A where EDX area analysis was performed. The EDX area analysis was performed on the region including the grains and grain boundaries. In the EDX area analysis, the carbon mapping image is shown in FIG. 37(B), the oxygen mapping image is shown in FIG. 37(C), Fluorine in Fig. 37(D), magnesium in Fig. 37(E), silicon in Fig. 37(F), phosphorus in Fig. Figure 38(A), sulfur in Figure 38(B), calcium in Figure 38(C), manganese in Figure 38(D ), cobalt is shown in Figure 38(E), and nickel is shown in Figure 38(F).
[0346] 37(B) to 37(F) and 38(A) to 38(F) show characteristics measured by EDX. The map shows the characteristic X-ray intensity, with measurement points with low characteristic X-ray intensity shown in light color (white) and The measurement points with higher X-ray intensity are shown in darker (black) colors. In other words, the measurement points with lighter (white) colors are The dark (black) measurement points indicate a low atomic concentration, while the dark (black) measurement points indicate a high atomic concentration. 7(B) to 37(F) and 38(A) to 38(F) show the distribution within the region. As shown in Fig. 1, the scale of the characteristic X-ray intensity is changed for each element.
[0347] As shown in Figures 37(B) to 37(F) and Figures 38(A) to 38(F), At and near the site, there are high concentrations of fluorine, magnesium, silicon and calcium. It was confirmed that silicon and calcium were contained in the reagents used as raw materials. It is believed that there were.
[0348] EDX area analysis shown in Figs. 37(B) to 37(F) and Figs. 38(A) to 38(F) The data of the linear region is extracted from the data, and the distribution of atomic concentration within the positive electrode active material particles is evaluated. Ta.
[0349] FIG. 33(B) shows an HAADF-STEM image of the area of sample A where EDX line analysis was performed. In FIG. 33(B), the area where the EDX line analysis was performed is indicated by an arrow. The analysis was performed on the crystal grains, the grain boundaries, and the regions spanning the crystal grains.
[0350] The carbon atom concentration in the EDX line analysis of the area shown in FIG. 33(B) is shown in FIG. 39(A). Oxygen in Fig. 39(B), fluorine in Fig. 39(C), magnesium in Fig. 39(D), silicon in Fig. Figure 39(E), phosphorus in Figure 39(F), sulfur in Figure 40(A), calcium in Figure 40(B), Manganese is shown in Figure 40(C), cobalt in Figure 40(D), and nickel in Figure 40(E).
[0351] In Figures 39(A) to 39(F) and 40(A) to 40(E), the horizontal axis represents distance ( The vertical axis indicates the atomic concentration [atomic%]. The distance is measured from the black circle at one end of the arrow shown in FIG. 33(B) as the starting point (distance = 0 nm) to the other end The vertical axis shows the atomic concentration of carbon, oxygen, etc. , fluorine, magnesium, silicon, phosphorus, sulfur, calcium, manganese, cobalt and The number of atoms of each element when the total number of nickel atoms is 100 atomic % The ratio of
[0352] As shown in FIG. 33(B), FIG. 39(A) to FIG. 39(F), and FIG. 40(A) to FIG. 40(E), As shown in Fig. 1, compared with the grain region, the grain boundaries and their vicinity are rich in fluorine, magnesium, and silicon. It was also confirmed that the concentrations of calcium and arsenic in the grain boundaries and their vicinity were high. It was found that the vicinity had a region with a width of 1 nm or more and 10 nm or less.
[0353] It was confirmed that the grain boundaries and their vicinity contained oxygen, magnesium, and fluorine. It was found that the grain boundaries and their vicinity contained magnesium oxide. It is believed that some of the oxygen in the silicon is replaced by fluorine.
[0354] On the other hand, in the grain region, fluorine, magnesium, silicon and calcium were at the detection limit. It was Lu.
[0355] Phosphorus and sulfur were at the lower detection limit both in the grains and at the grain boundaries.
[0356] Carbon was detected in the crystal grains and grain boundaries, but the carbon coating film was not used as a protective film. The carbon concentration mentioned above is thought to include carbon originating from the carbon coating film. Therefore, the true carbon concentration of the grains and grain boundaries could not be determined.
[0357] Compared to the grains, the grain boundaries and their vicinity are dominated by the transition metals manganese, cobalt, and nickel. It was confirmed that the atomic concentration of Kel was lower.
[0358] The total atomic concentration of the transition metals nickel, manganese, and cobalt is shown in Figure 40(F). In FIG. 40(F), the horizontal axis indicates distance (nm) and the vertical axis indicates nickel. Total atomic concentration of nickel, manganese and cobalt (Ni+Mn+Co) [atomic%] In sample A, the total atomic concentration of nickel, manganese and cobalt (Ni+M n+Co) can be said to be the atomic concentration of the transition metal. It was found that the concentration of transition metal atoms at and near the grain boundaries tends to be lower than that in the other regions. In addition, in the crystal grain region, there is no large variation in the atomic concentration of the transition metal, and it is approximately It was found to be uniform.
[0359] The ratio of the atomic concentration of magnesium (Mg) to the atomic concentration of transition metals in the crystal grains is shown. In FIG. 41(A), the horizontal axis represents distance [nm]. The vertical axis shows the ratio of the atomic concentration of magnesium to the atomic concentration of transition metals in the grains ( Mg / Tr-Metal).
[0360] The atomic concentration of the transition metal in the grain (Tr-Metal) is The average atomic concentration of the metals was used. The area of the crystal grains used to calculate the average value is shown in Figure 40(F). is indicated by an arrow.
[0361] As shown in FIG. 41(A), the grain boundaries and their vicinity are characterized by the atomic concentration of the transition metal in the grains. The ratio of magnesium atomic concentration to the concentration (Mg / Tr-Metal) is 0.030 or more. Magnesium is segregated at and near the grain boundaries. It was found that the grain boundaries and their vicinity are believed to contain magnesium oxide. Sample A, which is one embodiment of the present invention, has magnesium oxide at and near the grain boundaries. The positive electrode active material particles become chemically and structurally stable, and the transition metal dissolves into the electrolyte. This can suppress the deterioration of the positive electrode active material, such as detachment and instability of the crystal structure. It is possible to prevent the active material particles from cracking. In addition, it is possible to prevent oxygen from being released from the positive electrode active material particles. By using such positive electrode active material particles, deterioration of the power storage device can be suppressed. In this way, a highly safe power storage device can be obtained. The amount of lithium contained in the positive electrode decreases, making the crystal structure of the positive electrode active material particles more susceptible to transformation. For this reason, sample A is particularly preferable as the positive electrode active material particles.
[0362] The atomic concentration of fluorine relative to the atomic concentration of transition metals (Tr-Metal) in the crystal grains The ratio is shown in FIG. 41(B). In FIG. 41(B), the horizontal axis is distance [n m], and the vertical axis represents the ratio of the atomic concentration of fluorine to the atomic concentration of transition metals in the crystal grains ( F / Tr-Metal).
[0363] As shown in FIG. 41(B), the grain boundaries and their vicinity are characterized by the atomic concentration of the transition metal in the grains. The ratio of fluorine atom concentration to fluorine concentration (F / Tr-Metal) is 0.030 or more. It was found that the presence of fluorine at and near the grain boundaries reduces the It was found that magnesium could be efficiently segregated in the vicinity of the layer.
[0364] The total atomic concentration of nickel, manganese and cobalt (Ni+Mn+ The ratio of the atomic concentration of magnesium (Mg) to that of Co is shown in FIG. In C), the horizontal axis indicates distance [nm], and the vertical axis indicates EDX measurement points. The ratio of magnesium atoms to the total atomic concentration of nickel, manganese, and cobalt per The concentration ratio (Mg / (Ni+Mn+Co)) is shown.
[0365] The total atomic concentration of nickel, manganese and cobalt (Ni+Mn+ Co) is the same as the data shown in FIG. 40(F).
[0366] As shown in FIG. 41(C), the grain boundaries and their vicinity are composed of nickel and manganese in the grains. The ratio of the atomic concentration of magnesium to the total atomic concentration of nickel and cobalt (Mg / (Ni+ It was found that there is an area where the Mn+Co) is 0.030 or more. It was found that magnesium was segregated in the vicinity.
[0367] The total atomic concentration of nickel, manganese and cobalt (Ni+Mn+ The ratio of the atomic concentration of fluorine to that of Co is shown in FIG. The horizontal axis shows the distance [nm], and the vertical axis shows the nickel The ratio of the atomic concentration of fluorine to the total atomic concentration of manganese and cobalt (F / (Ni +Mn+Co).
[0368] As shown in FIG. 41(D), the grain boundaries and their vicinity are characterized by the atomic concentration of the transition metal in the grains. The ratio of fluorine atom concentration to the concentration (F / (Ni+Mn+Co)) is 0.030 or more. It was found that the grain boundary and its vicinity have fluorine, which It was found that magnesium can be efficiently segregated in and around the area.
[0369] From this example, it was found that magnesium and fluorine were added to the starting material of the positive electrode active material particles. It has become clear that magnesium segregates at and near the grain boundaries of the positive electrode active material particles. The positive electrode active material particles according to one embodiment of the present invention have magnesium oxide at the grain boundaries and in their vicinity. By having this, the positive electrode active material particles are chemically and structurally stable, and structural changes caused by charging and discharging are prevented. In other words, the crystal structure of the positive electrode active material particles becomes more stable. This makes it possible to suppress the transformation of the crystal structure even when the charge and discharge are repeated. This can prevent cracks, which means that deterioration such as a decrease in capacity can be prevented.
[0370] Since the power storage device having such positive electrode active material particles is less susceptible to deterioration, it is suitable for portable electronic devices. Furthermore, if it is applied to automobiles and other vehicles, it can be used to reduce the need for commercial power sources during peak power demand periods. This can also help to reduce energy consumption and carbon dioxide emissions. In addition, the power storage device can be highly safe. EXAMPLES
[0371] In this embodiment, a positive electrode active material having magnesium, fluorine, and oxygen at and near the grain boundaries is used. The crystal grains and crystallites in the active material were identified by TEM observation and STEM-EDX analysis. The concentration distribution of the grain boundaries was confirmed. The sample was one of sample B, which is one embodiment of the present invention. As material B, a cobalt oxide having magnesium, fluorine and oxygen at and near the grain boundaries is used. Lithium was produced. The composition of lithium cobalt oxide was assumed to be LiCoO2. LiCo O2 has a layered rock-salt type crystal structure.
[0372] <Preparation of Sample B> The preparation of sample B will be described.
[0373] As shown in step S11 of the flow in FIG. 3, starting materials were prepared. Charcoal was used as a lithium source. Lithium oxide (Li2CO3), tricobalt tetroxide (Co3O4) as a cobalt source, mag Magnesium oxide (MgO) as the potassium source, lithium fluoride (LiF Specifically, 3.1489 g (42.62 mmol) of Li2CO3 and 3.1489 g (42.62 mmol) of C 6.7726 g (28.13 mmol) of O3O4 and 0.0344 g (0.85 mmol) of MgO 0.0442 g (1.70 mmol) of LiF was weighed out. The ratio m of the number of magnesium atoms to the number of atoms of magnesium is 0.010 (1.0%). In addition, the ratio of the number of fluorine atoms to the number of magnesium atoms, n, is 2.0. The Li2CO3 used was manufactured by Kojundo Chemical Laboratory (catalog number: LIH06XB). The MgO used was manufactured by Kojundo Chemical Laboratory Co., Ltd. (catalog number: MGO12PB). F was manufactured by Kojundo Chemical Laboratory Co., Ltd. (catalog number: LIH10XB).
[0374] Next, as shown in step S12, the starting materials weighed in step S11 were mixed. Details of the mixing can be found in the description of Sample A, so a detailed explanation will be omitted.
[0375] Next, as shown in step S13, the material mixed in step S12 is subjected to a first heating. For details about the first heating, the description of Sample A can be referred to, and therefore the description will be omitted.
[0376] Next, as shown in step S14, the material heated in step S13 is cooled to room temperature, Synthetic product 2 was obtained. After cooling, the obtained synthetic product 2 was crushed to reduce the particle size of synthetic product 2. A 53 μm mesh was used for the crushing process.
[0377] Next, as shown in step S15, the second heating was performed on the composition 2 obtained in step S14. Since the details of the second heating can be referred to the description of sample A, the description is omitted.
[0378] By performing the second heating in step S15, magnesium and fluorine contained in the starting materials can be promoted to segregate at the grain boundaries of lithium cobaltate.
[0379] Next, as shown in step S16, the composition 2 heated in step S15 was cooled to room temperature and recovered to obtain sample B.
[0380] <TEM Observation, STEM Observation, EDX Measurement> Next, sample B was thinned by focused ion beam (FIB), and the cross-section of sample B was observed by TEM and STEM. Also, the cross-section of sample B was subjected to composition analysis by EDX measurement. Since the details of TEM, STEM observation and EDX measurement can be referred to the description of sample A, the description is omitted.
[0381] The TEM image (bright field image) of the cross-section of sample B is shown in Fig. 42(A). The magnification of Fig. 42(A) is 10 times 10,000. In Fig. 42(A), the region where the density (luminance) of the TEM image is substantially uniform has a substantially constant crystal orientation and is considered to be a single crystal. Also, the region where the density (luminance) of the TEM image changes is considered to be a grain boundary. A schematic diagram corresponding to Fig. 42(A) is shown in Fig. 42(B). As shown in Fig. 42(A) and Fig. 42(B), it was confirmed that the positive electrode active material particles have a plurality of crystal grains 1201 and grain boundaries 1203 between the crystal grains.
[0382] The STEM image (bright field image) of the cross-section of sample B is shown in Fig. 43(A), and HAADF-STE at the same location The M image is shown in Figure 43(B). The magnification of Figures 43(A) and 43(B) is 8 million times. In Figures 43(A) and 43(B), crystal lattice images were observed in the crystal grain regions.
[0383] FIG. 44(A) shows an HAADF-STEM image of the area of sample B where EDX area analysis was performed. The EDX area analysis was performed in a region including crystal grains and crystal grain boundaries. Measurements were taken at 256 vertical x 256 horizontal points within the region.
[0384] Carbon, oxygen, fluorine, magnesium, silicon, phosphorus, sulfur, calcium, manganese, cobalt Peaks due to electronic transitions to the K shells of barium, nickel, and nickel were observed. The spectra were separated into individual elements to obtain their atomic concentrations.
[0385] The carbon mapping image in the EDX area analysis of the area shown in FIG. 44(A) is shown in FIG. 44(B). ), oxygen in Fig. 44(C), fluorine in Fig. 44(D), magnesium in Fig. 44(E), silicon Figure 44(F) for cation, Figure 45(A) for phosphorus, Figure 45(B) for sulfur, Figure 45(C) for calcium. ), and cobalt is shown in Figure 45(D).
[0386] 44(B) to 44(F) and 45(A) to 45(D) show characteristics measured by EDX. The map shows the characteristic X-ray intensity, with measurement points with low characteristic X-ray intensity shown in light color (white) and The measurement points with higher X-ray intensity are shown in darker (black) colors. In other words, the measurement points with lighter (white) colors are The dark (black) measurement points indicate a high atomic concentration, while the low atomic concentration points indicate a low atomic concentration. 4(B) to 44(F) and 45(A) to 45(D) show the distribution within the region. As shown in Fig. 1, the scale of the characteristic X-ray intensity is changed for each element.
[0387] As shown in Figures 44(B) to 44(F) and Figures 45(A) to 45(D), It was confirmed that the concentrations of magnesium and calcium were high in and around the area. As for fluorine, it was hardly observed in the area where EDX analysis was performed. This is thought to be because fluorine, a light element, is difficult to detect using EDX. It is believed that the compound was contained in the reagents used as raw materials.
[0388] EDX area analysis shown in Figs. 44(B) to 44(F) and Figs. 45(A) to 45(D) The data of the linear region is extracted from the data, and the distribution of atomic concentration within the positive electrode active material particles is evaluated. Ta.
[0389] FIG. 46(A) shows an HAADF-STEM image of the area of sample B where EDX line analysis was performed. In FIG. 46(A), the area where the EDX line analysis was performed is indicated by an arrow. The analysis was performed on the crystal grains, the grain boundaries, and the regions spanning the crystal grains.
[0390] The carbon atom concentration in the EDX line analysis of the area shown in FIG. 46(A) is shown in FIG. 47(A). Oxygen in Fig. 47(B), fluorine in Fig. 47(C), magnesium in Fig. 47(D), silicon in Fig. Fig. 47(E), Phosphorus Fig. 47(F), Sulfur Fig. 48(A), Calcium Fig. 48(B), Cobalt is shown in Figure 48(C).
[0391] In Figures 47(A) to 47(F) and Figures 48(A) to 48(C), the horizontal axis represents distance ( The vertical axis indicates the atomic concentration [atomic%]. The distance is measured from the black circle at one end of the arrow shown in FIG. 46(A) as the starting point (distance = 0 nm) to the other end The vertical axis shows the atomic concentration of carbon, oxygen, etc. , fluorine, magnesium, silicon, phosphorus, sulfur, calcium and cobalt atoms The ratio of the number of atoms of each element is shown, assuming that the number of atoms is 100 atomic %.
[0392] As shown in FIG. 46(A), FIG. 47(A) to FIG. 47(F), FIG. 48(A) to FIG. 48(C), As shown in Fig. 1, the grain boundaries and their vicinity are rich in magnesium and calcium compared to the grain regions. It was confirmed that the concentration was high. In addition, the grain boundaries and their vicinity were characterized by a width of 1 nm or less. It was found that the region was 10 nm or less above the surface.
[0393] It was confirmed that the grain boundaries and their vicinity contained oxygen and magnesium. It was found that the surface and its surroundings contained magnesium oxide.
[0394] On the other hand, in the grain region, fluorine, magnesium, silicon and calcium were at the detection limit. It was Lu.
[0395] Phosphorus and sulfur were at the lower detection limit both in the grains and at the grain boundaries.
[0396] Carbon was detected in the crystal grains and grain boundaries, but the carbon coating film was not used as a protective film. The carbon concentration mentioned above is thought to include carbon originating from the carbon coating film. Therefore, the true carbon concentration of the grains and grain boundaries could not be determined.
[0397] Compared to the crystal grains, the grain boundaries and their vicinity have a lower atomic concentration of cobalt, which is a transition metal. We were able to confirm that this was the case.
[0398] In sample B, the atomic concentration of cobalt can also be said to be the atomic concentration of transition metals. As shown in Fig. 1, the grain boundaries and their vicinity have a higher atomic concentration of transition metals than the grain regions. In addition, the atomic concentration of transition metals in the grain region was found to be low. It was found that there was no significant variation and the results were approximately uniform.
[0399] The ratio of the atomic concentration of magnesium (Mg) to the atomic concentration of transition metals in the crystal grains is shown. In FIG. 49(A), the horizontal axis represents distance [nm]. The vertical axis shows the ratio of the atomic concentration of magnesium to the atomic concentration of transition metals in the grains ( Mg / Tr-Metal).
[0400] The atomic concentration of the transition metal in the grain (Tr-Metal) is The average atomic concentration of the metals was used. The area of the crystal grains used to calculate the average value is shown in Figure 48(D). is indicated by an arrow.
[0401] As shown in FIG. 49(A), the grain boundaries and their vicinity are characterized by the atomic concentration of the transition metal in the grains. The ratio of magnesium atomic concentration to the concentration (Mg / Tr-Metal) is 0.030 or more. Magnesium is segregated at and near the grain boundaries. It was found that the grain boundaries and their vicinity are believed to contain magnesium oxide. Sample B, which is one embodiment of the present invention, has magnesium oxide at and near the grain boundaries. The positive electrode active material particles become chemically and structurally stable, and the transition metal dissolves into the electrolyte. This can suppress the deterioration of the positive electrode active material, such as detachment and instability of the crystal structure. It is possible to prevent the active material particles from cracking. In addition, it is possible to prevent oxygen from being released from the positive electrode active material particles. By using such positive electrode active material particles, deterioration of the power storage device can be suppressed. In this way, a highly safe power storage device can be obtained. The amount of lithium contained in the positive electrode decreases, making the crystal structure of the positive electrode active material particles more susceptible to transformation. For this reason, sample B is particularly preferable as the positive electrode active material particles.
[0402] The atomic concentration of fluorine relative to the atomic concentration of transition metals (Tr-Metal) in the crystal grains The ratio is shown in Figure 49(B). In Figure 49(B), the horizontal axis is distance [n m], and the vertical axis represents the ratio of the atomic concentration of fluorine to the atomic concentration of transition metals in the crystal grains ( F / Tr-Metal).
[0403] As shown in FIG. 47(C) and FIG. 49(B), in sample B, the grains and grain boundaries The fluorine concentration was below the detection limit. Fluorine is a light element and is difficult to detect by EDX. It is considered that.
[0404] The atomic concentration of magnesium (Mg) relative to the atomic concentration of cobalt (Co) at each EDX measurement point. The ratio of the molecular concentrations is shown in FIG. 49(C). In FIG. 49(C), the horizontal axis is distance (Distance e) [nm], and the vertical axis shows the magnetic field versus the atomic concentration of cobalt at each EDX measurement point. The ratio of the atomic concentrations of magnesium and cobalt (Mg / Co) is shown.
[0405] As shown in FIG. 49(C), the grain boundaries and their vicinity are the same in terms of the cobalt atomic concentration in the grains. The ratio of magnesium atom concentration to the concentration (Mg / Co) is 0.030 or more. It was found that magnesium was segregated at and near the grain boundaries. I did.
[0406] The ratio of the atomic concentration of fluorine to the atomic concentration of cobalt (Co) at each EDX measurement point is shown. In FIG. 49(D), the horizontal axis represents distance [nm]. The vertical axis shows the ratio of the atomic concentration of fluorine to the atomic concentration of cobalt at each EDX measurement point. In sample B, the fluorine concentration in the grains and grain boundaries was below the detection limit. It was below.
[0407] Similarly, EDX measurement was performed on another portion of sample B.
[0408] FIG. 50(A) shows an HAADF-STEM image of the area of sample B where EDX area analysis was performed. The EDX area analysis was performed on the region including the grains and grain boundaries. In the EDX area analysis, the carbon mapping image is shown in Fig. 50(B), the oxygen mapping image is shown in Fig. 50(C), Fluorine in Fig. 50(D), magnesium in Fig. 50(E), silicon in Fig. 50(F), phosphorus in Fig. Figure 51(A), sulfur in Figure 51(B), calcium in Figure 51(C), cobalt in Figure 51(D ) as shown in
[0409] 50(B) to 50(F) and 51(A) to 51(D) show characteristics obtained by EDX measurement. The map shows the characteristic X-ray intensity, with measurement points with low characteristic X-ray intensity shown in light color (white) and The measurement points with higher X-ray intensity are shown in darker (black) colors. In other words, the measurement points with lighter (white) colors are The dark (black) measurement points indicate a high atomic concentration, while the low atomic concentration points indicate a low atomic concentration. 0(B) to 50(F) and 51(A) to 51(D) show the distribution within the region in a clear manner. As shown in Fig. 1, the scale of the characteristic X-ray intensity is changed for each element.
[0410] As shown in Figures 50(B) to 50(F) and Figures 51(A) to 51(D), grain boundaries It was confirmed that the concentrations of magnesium and calcium were high in and around the area. As for fluorine, it was hardly observed in the area where EDX analysis was performed. This is thought to be because fluorine, a light element, is difficult to detect using EDX. It is believed that the compound was contained in the reagents used as raw materials.
[0411] EDX area analysis shown in Figs. 50(B) to 50(F) and Figs. 51(A) to 51(D) The data of the linear region is extracted from the data, and the distribution of atomic concentration within the positive electrode active material particles is evaluated. Ta.
[0412] FIG. 46(B) shows an HAADF-STEM image of the area of sample B where EDX line analysis was performed. In FIG. 46(B), the area where the EDX line analysis was performed is indicated by an arrow. The analysis was performed on the crystal grains, the grain boundaries, and the regions spanning the crystal grains.
[0413] The carbon atom concentration in the EDX line analysis of the area shown in FIG. 46(B) is shown in FIG. 52(A). Oxygen in Fig. 52(B), fluorine in Fig. 52(C), magnesium in Fig. 52(D), silicon in Fig. Fig. 52(E), Phosphorus Fig. 52(F), Sulfur Fig. 53(A), Calcium Fig. 53(B), Cobalt is shown in Figure 53(C).
[0414] In Figures 52(A) to 52(F) and Figures 53(A) to 53(C), the horizontal axis represents distance ( The vertical axis indicates the atomic concentration [atomic%]. The distance is measured from the black circle at one end of the arrow shown in FIG. 46(B) as the starting point (distance = 0 nm) to the other end The vertical axis shows the atomic concentration of carbon, oxygen, etc. , fluorine, magnesium, silicon, phosphorus, sulfur, calcium and cobalt atoms The ratio of the number of atoms of each element is shown, assuming that the number of atoms is 100 atomic %.
[0415] As shown in FIG. 46(B), FIG. 52(A) to FIG. 52(F), and FIG. 53(A) to FIG. 53(C), As shown in Fig. 1, the grain boundaries and their vicinity have a higher magnesium concentration than the grain regions. It was also confirmed that the grain boundaries and their vicinity have a width of 1 nm to 10 nm. It was found that the region was
[0416] It was confirmed that the grain boundaries and their vicinity contained oxygen and magnesium. It was found that the surface and its surroundings contained magnesium oxide.
[0417] On the other hand, in the grain region, fluorine, magnesium, silicon and calcium were at the detection limit. It was Lu.
[0418] Phosphorus and sulfur were at the lower detection limit both in the grains and at the grain boundaries.
[0419] Carbon was detected in the crystal grains and grain boundaries, but the carbon coating film was not used as a protective film. The carbon concentration mentioned above is thought to include carbon originating from the carbon coating film. Therefore, the true carbon concentration of the grains and grain boundaries could not be determined.
[0420] Compared to the crystal grains, the grain boundaries and their vicinity have a lower atomic concentration of cobalt, which is a transition metal. We were able to confirm that this was the case.
[0421] In sample B, the atomic concentration of cobalt can also be said to be the atomic concentration of transition metals. As shown in Fig. 1, the grain boundaries and their vicinity have a higher atomic concentration of transition metals than the grain regions. In addition, the atomic concentration of transition metals in the grain region was found to be low. It was found that there was no significant variation and the results were approximately uniform.
[0422] The ratio of the atomic concentration of magnesium (Mg) to the atomic concentration of transition metals in the crystal grains is shown. In FIG. 54(A), the horizontal axis represents distance [nm]. The vertical axis shows the ratio of the atomic concentration of magnesium to the atomic concentration of transition metals in the grains ( Mg / Tr-Metal).
[0423] The atomic concentration of the transition metal in the grain (Tr-Metal) is The average atomic concentration of the metals was used. The area of the crystal grains used to calculate the average value is shown in Figure 53(D). is indicated by an arrow.
[0424] As shown in FIG. 54(A), the grain boundaries and their vicinity are characterized by the atomic concentration of the transition metal in the grains. The ratio of magnesium atomic concentration to the concentration (Mg / Tr-Metal) is 0.030 or more. Magnesium is segregated at and near the grain boundaries. It was found that the grain boundaries and their vicinity are believed to contain magnesium oxide. Sample B, which is one embodiment of the present invention, has magnesium oxide at and near the grain boundaries. The positive electrode active material particles become chemically and structurally stable, and the transition metal dissolves into the electrolyte. This can suppress the deterioration of the positive electrode active material, such as detachment and instability of the crystal structure. It is possible to prevent the active material particles from cracking. In addition, it is possible to prevent oxygen from being released from the positive electrode active material particles. By using such positive electrode active material particles, deterioration of the power storage device can be suppressed. In this way, a highly safe electricity storage device can be obtained. Since the crystal structure of the positive electrode active material particles is easily transformed, sample B is particularly preferable as the positive electrode active material particles. .
[0425] The atomic concentration of fluorine relative to the atomic concentration of transition metals (Tr-Metal) in the crystal grains The ratio is shown in Figure 54(B). In Figure 54(B), the horizontal axis is distance [n m], and the vertical axis represents the ratio of the atomic concentration of fluorine to the atomic concentration of transition metals in the crystal grains ( F / Tr-Metal).
[0426] As shown in FIG. 52(C) and FIG. 54(B), in sample B, the grains and grain boundaries The fluorine concentration was below the detection limit. Fluorine is a light element and is difficult to detect by EDX. It is considered that.
[0427] The atomic concentration of magnesium (Mg) relative to the atomic concentration of cobalt (Co) at each EDX measurement point. The ratio of the molecular concentrations is shown in FIG. 54(C). In FIG. 54(C), the horizontal axis is distance (Distance e) [nm], and the vertical axis shows the magnetic field versus the atomic concentration of cobalt at each EDX measurement point. The ratio of the atomic concentrations of magnesium and cobalt (Mg / Co) is shown.
[0428] As shown in FIG. 54(C), the grain boundaries and their vicinity are the same in terms of the cobalt atomic concentration in the grains. The ratio of magnesium atom concentration to the concentration (Mg / Co) is 0.030 or more. It was found that magnesium was segregated at and near the grain boundaries. I did.
[0429] The ratio of the atomic concentration of fluorine to the atomic concentration of cobalt (Co) at each EDX measurement point is shown. In FIG. 54(D), the horizontal axis represents distance [nm]. The vertical axis shows the ratio of the atomic concentration of fluorine to the atomic concentration of cobalt at each EDX measurement point. In sample B, the fluorine concentration in the grains and grain boundaries was below the detection limit. It was below. [Explanation of symbols]
[0430] 100: positive electrode active material particle, 101: crystal grain, 103: crystal grain boundary, 105: crystal defect, 10 7: region, 200: active material layer, 201: graphene compound, 211a: positive electrode, 211b: Negative electrode, 212a: lead, 212b: lead, 214: separator, 215a: joint, 215b: joint, 217: fixing member, 250: battery, 251: exterior body, 261: folding ridge, 262: seal, 263: seal, 271: ridgeline, 272: valley line, 273: void Between the battery, 300: secondary battery, 301: positive electrode can, 302: negative electrode can, 303: gasket, 304 : Positive electrode, 305: Positive electrode current collector, 306: Positive electrode active material layer, 307: Negative electrode, 308: Negative electrode current collector body, 309: negative electrode active material layer, 310: separator, 500: secondary battery, 501: positive electrode current collector body, 502: positive electrode active material layer, 503: positive electrode, 504: negative electrode current collector, 505: negative electrode active material layer 506: negative electrode, 507: separator, 508: electrolyte, 509: exterior body, 510: positive electrode Lead electrode, 511: negative electrode lead electrode, 600: secondary battery, 601: positive electrode cap, 60 2: battery can, 603: positive electrode terminal, 604: positive electrode, 605: separator, 606: negative electrode, 6 07: negative terminal, 608: insulating plate, 609: insulating plate, 611: PTC element, 612: safety Valve mechanism, 900: circuit board, 910: label, 911: terminal, 912: circuit, 913: Next battery, 914: antenna, 915: antenna, 916: layer, 917: layer, 918: antenna Tena, 919: terminal, 920: display device, 921: sensor, 922: terminal, 930: housing , 930a: housing, 930b: housing, 931: negative electrode, 932: positive electrode, 933: separator , 950: Winding body, 951: Terminal, 952: Terminal, 980: Secondary battery, 993: Winding body, 994: negative electrode, 995: positive electrode, 996: separator, 997: lead electrode, 998: lead electrode, 1101: crystal grain, 1103: crystal grain boundary, 1201: crystal grain, 1203: crystal grain 7100: Portable display device, 7101: Housing, 7102: Display unit, 7103: Operation button 7104: secondary battery, 7200: mobile information terminal, 7201: housing, 7202: display unit , 7203: Band, 7204: Buckle, 7205: Operation button, 7206: Input / output terminal child, 7207: icon, 7300: display device, 7304: display unit, 7400: mobile phone 7401: Housing, 7402: Display unit, 7403: Operation buttons, 7404: External connection port 7405: Speaker, 7406: Microphone, 7407: Secondary battery, 8000: Display 8001: housing, 8002: display unit, 8003: speaker unit, 8004: secondary battery, 8021: charging device, 8022: cable, 8024: secondary battery, 8100: lighting device, 8101: Housing, 8102: Light source, 8103: Secondary battery, 8104: Ceiling, 8105: Side Wall, 8106: Floor, 8107: Window, 8200: Indoor unit, 8201: Housing, 8202: Fan 8203: Secondary battery, 8204: Outdoor unit, 8300: Electric refrigerator / freezer, 8301: Case Body, 8302: refrigerator door, 8303: freezer door, 8304: secondary battery, 8400: electric vehicles, 8401: headlights, 8406: electric motors, 8500: automobiles, 8600 : Scooter, 8601: Side mirror, 8602: Secondary battery, 8603: Turn signal light, 8 604: Under-seat storage, 9600: Tablet, 9625: Switch, 9626: switch, 9627: power switch, 9628: operation switch, 9629: fastener, 963 0: Housing, 9630a: Housing, 9630b: Housing, 9631: Display, 9633: Solar cell 9634: Charge / discharge control circuit, 9635: Power storage body, 9636: DCDC converter, 9 637: Converter, 9640: Moving part
Claims
1. A lithium ion secondary battery comprising a positive electrode having positive electrode active material particles and a negative electrode, The positive electrode active material particles include lithium cobalt oxide, The positive electrode active material particles have a plurality of crystal grains, the positive electrode active material particles have grain boundaries between adjacent grains, the grain boundaries comprise magnesium, fluorine, and oxygen; the positive electrode active material particles have regions at the grain boundaries where the magnesium concentration is higher than that of regions of the crystal grains, the grain boundaries have regions in which a ratio of the atomic concentration of magnesium to the atomic concentration of cobalt at each measurement point in energy dispersive X-ray analysis is 0.030 or more.
2. A lithium ion secondary battery comprising a positive electrode having positive electrode active material particles and a negative electrode, The positive electrode active material particles include lithium cobalt oxide, The positive electrode active material particles have a plurality of crystal grains, the positive electrode active material particles have grain boundaries between adjacent grains, the grain boundaries comprise magnesium oxide; the positive electrode active material particles have regions at the grain boundaries where the magnesium concentration is higher than that of regions of the crystal grains, the grain boundaries have regions in which a ratio of the atomic concentration of magnesium to the atomic concentration of cobalt at each measurement point in energy dispersive X-ray analysis is 0.030 or more.
3. A lithium ion secondary battery comprising a positive electrode having positive electrode active material particles and a negative electrode, The positive electrode active material particles include lithium cobalt oxide, The positive electrode active material particles have a plurality of crystal grains, the positive electrode active material particles have grain boundaries between adjacent grains, the grain boundaries comprise magnesium, fluorine, oxygen, and silicon; the positive electrode active material particles have regions at the grain boundaries where the magnesium concentration is higher than that of regions of the crystal grains, the grain boundaries have regions in which a ratio of the atomic concentration of magnesium to the atomic concentration of cobalt at each measurement point in energy dispersive X-ray analysis is 0.030 or more.
4. A lithium ion secondary battery comprising a positive electrode having positive electrode active material particles and a negative electrode, The positive electrode active material particles include lithium cobalt oxide, The positive electrode active material particles have a plurality of crystal grains, the positive electrode active material particles have grain boundaries between adjacent grains, the grain boundaries include magnesium oxide and silicon; the positive electrode active material particles have regions at the grain boundaries where the magnesium concentration is higher than that of regions of the crystal grains, the grain boundaries have regions in which a ratio of the atomic concentration of magnesium to the atomic concentration of cobalt at each measurement point in energy dispersive X-ray analysis is 0.030 or more.
5. A lithium ion secondary battery comprising a positive electrode having positive electrode active material particles and a negative electrode, The positive electrode active material particles include lithium cobalt oxide, The positive electrode active material particles have a plurality of crystal grains, the positive electrode active material particles have grain boundaries between adjacent grains, the grain boundaries include magnesium, fluorine, oxygen, and calcium; the positive electrode active material particles have regions at the grain boundaries where the magnesium concentration is higher than that of regions of the crystal grains, the grain boundaries have regions in which a ratio of the atomic concentration of magnesium to the atomic concentration of cobalt at each measurement point in energy dispersive X-ray analysis is 0.030 or more.
6. A lithium ion secondary battery comprising a positive electrode having positive electrode active material particles and a negative electrode, The positive electrode active material particles include lithium cobalt oxide, The positive electrode active material particles have a plurality of crystal grains, the positive electrode active material particles have grain boundaries between adjacent grains, The grain boundaries include magnesium oxide and calcium, the positive electrode active material particles have regions at the grain boundaries where the magnesium concentration is higher than that of regions of the crystal grains, the grain boundaries have regions in which a ratio of the atomic concentration of magnesium to the atomic concentration of cobalt at each measurement point in energy dispersive X-ray analysis is 0.030 or more.
7. A lithium ion secondary battery comprising a positive electrode having positive electrode active material particles and a negative electrode, The positive electrode active material particles include lithium cobalt oxide, The positive electrode active material particles have a plurality of crystal grains, the positive electrode active material particles have grain boundaries between adjacent grains, the grain boundaries include magnesium, fluorine, oxygen, silicon, and calcium; the positive electrode active material particles have regions at the grain boundaries where the magnesium concentration is higher than that of regions of the crystal grains, the grain boundaries have regions in which a ratio of the atomic concentration of magnesium to the atomic concentration of cobalt at each measurement point in energy dispersive X-ray analysis is 0.030 or more.
8. A lithium ion secondary battery comprising a positive electrode having positive electrode active material particles and a negative electrode, The positive electrode active material particles include lithium cobalt oxide, The positive electrode active material particles have a plurality of crystal grains, the positive electrode active material particles have grain boundaries between adjacent grains, the grain boundaries include magnesium oxide, silicon, and calcium; the positive electrode active material particles have regions at the grain boundaries where the magnesium concentration is higher than that of regions of the crystal grains, the grain boundaries have regions in which a ratio of the atomic concentration of magnesium to the atomic concentration of cobalt at each measurement point in energy dispersive X-ray analysis is 0.030 or more.
9. A lithium ion secondary battery comprising a positive electrode having positive electrode active material particles and a negative electrode, The positive electrode active material particles include lithium cobalt oxide, the positive electrode active material particles have a first region in which a magnesium atomic concentration is detected to exceed a lower limit of detection by energy dispersive X-ray analysis, and a second region in which the magnesium atomic concentration is at a lower limit of detection by energy dispersive X-ray analysis, the first region has a grain boundary; the second region has grains; the grain boundary is located between adjacent grains across the grain boundary, the grain boundaries comprise magnesium, fluorine, and oxygen; the positive electrode active material particles have regions at the grain boundaries where the magnesium concentration is higher than that of regions of the crystal grains, the grain boundaries have regions in which a ratio of the atomic concentration of magnesium to the atomic concentration of cobalt at each measurement point in the energy dispersive X-ray analysis is 0.030 or more.
10. A lithium ion secondary battery comprising a positive electrode having positive electrode active material particles and a negative electrode, The positive electrode active material particles include lithium cobalt oxide, the positive electrode active material particles have a first region in which a magnesium atomic concentration is detected to exceed a lower limit of detection by energy dispersive X-ray analysis, and a second region in which the magnesium atomic concentration is at a lower limit of detection by energy dispersive X-ray analysis, the first region has a grain boundary; the second region has grains; the grain boundary is located between adjacent grains across the grain boundary, the grain boundaries comprise magnesium oxide; the positive electrode active material particles have regions at the grain boundaries where the magnesium concentration is higher than that of regions of the crystal grains, the grain boundaries have regions in which a ratio of the atomic concentration of magnesium to the atomic concentration of cobalt at each measurement point in the energy dispersive X-ray analysis is 0.030 or more.
11. A lithium ion secondary battery comprising a positive electrode having positive electrode active material particles and a negative electrode, The positive electrode active material particles include lithium cobalt oxide, the positive electrode active material particles have a first region in which a magnesium atomic concentration is detected to exceed a lower limit of detection by energy dispersive X-ray analysis, and a second region in which the magnesium atomic concentration is at a lower limit of detection by energy dispersive X-ray analysis, the first region has a grain boundary; the second region has grains; the grain boundary is located between adjacent grains across the grain boundary, the grain boundaries comprise magnesium, fluorine, oxygen, and silicon; the positive electrode active material particles have regions at the grain boundaries where the magnesium concentration is higher than that of regions of the crystal grains, the grain boundaries have regions in which a ratio of the atomic concentration of magnesium to the atomic concentration of cobalt at each measurement point in the energy dispersive X-ray analysis is 0.030 or more.
12. A lithium ion secondary battery comprising a positive electrode having positive electrode active material particles and a negative electrode, The positive electrode active material particles include lithium cobalt oxide, the positive electrode active material particles have a first region in which a magnesium atomic concentration is detected to exceed a lower limit of detection by energy dispersive X-ray analysis, and a second region in which the magnesium atomic concentration is at a lower limit of detection by energy dispersive X-ray analysis, the first region has a grain boundary; the second region has grains; the grain boundary is located between adjacent grains across the grain boundary, the grain boundaries include magnesium oxide and silicon; the positive electrode active material particles have regions at the grain boundaries where the magnesium concentration is higher than that of regions of the crystal grains, the grain boundaries have regions in which a ratio of the atomic concentration of magnesium to the atomic concentration of cobalt at each measurement point in the energy dispersive X-ray analysis is 0.030 or more.
13. A lithium ion secondary battery comprising a positive electrode having positive electrode active material particles and a negative electrode, The positive electrode active material particles include lithium cobalt oxide, the positive electrode active material particles have a first region in which a magnesium atomic concentration is detected to exceed a lower limit of detection by energy dispersive X-ray analysis, and a second region in which the magnesium atomic concentration is at a lower limit of detection by energy dispersive X-ray analysis, the first region has a grain boundary; the second region has grains; the grain boundary is located between adjacent grains across the grain boundary, the grain boundaries include magnesium, fluorine, oxygen, and calcium; the positive electrode active material particles have regions at the grain boundaries where the magnesium concentration is higher than that of regions of the crystal grains, the grain boundaries have regions in which a ratio of the atomic concentration of magnesium to the atomic concentration of cobalt at each measurement point in the energy dispersive X-ray analysis is 0.030 or more.
14. A lithium ion secondary battery comprising a positive electrode having positive electrode active material particles and a negative electrode, The positive electrode active material particles include lithium cobalt oxide, the positive electrode active material particles have a first region in which a magnesium atomic concentration is detected to exceed a lower limit of detection by energy dispersive X-ray analysis, and a second region in which the magnesium atomic concentration is at a lower limit of detection by energy dispersive X-ray analysis, the first region has a grain boundary; the second region has grains; the grain boundary is located between adjacent grains across the grain boundary, The grain boundaries include magnesium oxide and calcium, the positive electrode active material particles have regions at the grain boundaries where the magnesium concentration is higher than that of regions of the crystal grains, the grain boundaries have regions in which a ratio of the atomic concentration of magnesium to the atomic concentration of cobalt at each measurement point in the energy dispersive X-ray analysis is 0.030 or more.
15. A lithium ion secondary battery comprising a positive electrode having positive electrode active material particles and a negative electrode, The positive electrode active material particles include lithium cobalt oxide, the positive electrode active material particles have a first region in which a magnesium atomic concentration is detected to exceed a lower limit of detection by energy dispersive X-ray analysis, and a second region in which the magnesium atomic concentration is at a lower limit of detection by energy dispersive X-ray analysis, the first region has a grain boundary; the second region has grains; the grain boundary is located between adjacent grains across the grain boundary, the grain boundaries include magnesium, fluorine, oxygen, silicon, and calcium; the positive electrode active material particles have regions at the grain boundaries where the magnesium concentration is higher than that of regions of the crystal grains, the grain boundaries have regions in which a ratio of the atomic concentration of magnesium to the atomic concentration of cobalt at each measurement point in the energy dispersive X-ray analysis is 0.030 or more.
16. A lithium ion secondary battery comprising a positive electrode having positive electrode active material particles and a negative electrode, The positive electrode active material particles include lithium cobalt oxide, the positive electrode active material particles have a first region in which a magnesium atomic concentration is detected to exceed a lower limit of detection by energy dispersive X-ray analysis, and a second region in which the magnesium atomic concentration is at a lower limit of detection by energy dispersive X-ray analysis, the first region has a grain boundary; the second region has grains; the grain boundary is located between adjacent grains across the grain boundary, the grain boundaries include magnesium oxide, silicon, and calcium; the positive electrode active material particles have regions at the grain boundaries where the magnesium concentration is higher than that of regions of the crystal grains, the grain boundaries have regions in which a ratio of the atomic concentration of magnesium to the atomic concentration of cobalt at each measurement point in the energy dispersive X-ray analysis is 0.030 or more.
17. In any one of claims 9 to 16, The lower detection limit of the lithium ion secondary battery is 1 atomic %.
18. In any one of claims 9 to 16, The lithium ion secondary battery, wherein the detection limit is 1 atomic % when a Si drift detector is used for detecting X-rays in the energy dispersive X-ray analysis.
19. In any one of claims 1 to 18, The lithium cobalt oxide is a lithium ion secondary battery having a layered rock salt type crystal structure.
20. In any one of claims 1 to 19, The lithium ion secondary battery has an electrolyte, The lithium ion secondary battery, wherein the electrolyte comprises vinylene carbonate.
21. In any one of claims 1 to 20, The positive electrode has a conductive assistant, The lithium ion secondary battery, wherein the conductive assistant comprises carbon fiber.
22. In claim 21, The lithium ion secondary battery, wherein the carbon fiber is a carbon nanofiber or a carbon nanotube.
23. In any one of claims 1 to 20, The positive electrode has a conductive assistant, The conductive assistant has a region in surface contact with the positive electrode active material particles.
24. In any one of claims 1 to 23, The magnesium concentration is an atomic concentration of magnesium measured by the energy dispersive X-ray analysis.
25. In any one of claims 1 to 24, In the energy dispersive X-ray analysis, the beam diameter was set to 0.1 nmφ for the lithium ion secondary battery.
26. In any one of claims 1 to 25, A lithium ion secondary battery, wherein the atomic concentration indicates the ratio of the number of atoms of each element when the total number of atoms of carbon, oxygen, fluorine, magnesium, silicon, phosphorus, sulfur, calcium, and cobalt is taken as 100 atomic %.
27. In any one of claims 1 to 26, the positive electrode active material particles have regions at the grain boundaries having a lower atomic concentration of cobalt than regions of the crystal grains.
28. In any one of claims 1 to 27, The positive electrode has a coating, The coating has a region covering the positive electrode active material particles.
Citation Information
Patent Citations
New process for preparing high quality Co3O4
CN1715193A
Lithium nickel manganese layered composite oxide
JP2003068306A
Power storage device
JP2012018914A
Cathode active material showing improved characteristics at high voltage
JP2016054151A
Positive electrode active material for lithium ion secondary battery, and lithium ion secondary battery
JP2016076454A